Glass-ceramics, glass-ceramic articles and methods of making the same
By adjusting the component ratio of glass-ceramics and adding spinel crystal phase, the shortcomings of glass-ceramics in terms of mechanical and optical properties have been solved, resulting in glass-ceramic products with high mechanical strength and low haze, suitable for display devices and electronic devices.
Patent Information
- Application Number
- CN202310470769.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-27
- Publication Date
- 2025-11-25
- Estimated Expiration
- 2043-04-27
AI Technical Summary
Existing microcrystalline glass has shortcomings in terms of optical and mechanical properties, making it difficult to meet the requirements of high-demand display devices or electronic devices.
By adjusting the composition ratio of glass-ceramics, including the content of SiO2, Al2O3, Li2O, ZnO and TiO2, and adding clarifying agents, glass-ceramics containing spinel crystal phases can be prepared, thereby improving their mechanical and optical properties.
It achieves high mechanical strength, low haze and excellent light transmittance of microcrystalline glass, meeting the high mechanical and optical performance requirements of electronic devices.
Smart Images

Figure BDA0004203892430000391 
Figure BDA0004203892430000421 
Figure BDA0004203892430000431
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a glass-ceramic, in particular to a glass-ceramic with excellent mechanical properties and a glass-ceramic product, which is suitable for display devices or electronic devices. BACKGROUND
[0002] In recent years, glass-ceramics are often used in various displays and display devices of many electronic products, such as mobile phones, music players, e-book readers, notepads, tablets, notebook computers, automatic teller machines and other similar devices. The materials used to form the housings of display devices and electronic devices are usually selected to meet the mechanical requirements related to the end use of the electronic devices. On the other hand, electronic devices or display devices have higher requirements for the optical properties of the glass-ceramics used therein, which refer to the properties exhibited by a substance when it absorbs, reflects and refracts light, such as haze, |B| value, etc. However, the glass-ceramics on the market currently have problems such as high haze, which are difficult to apply to display devices or electronic devices with higher optical performance requirements. SUMMARY
[0003] The technical problem to be solved by the present application is to provide a glass-ceramic with excellent mechanical properties and a glass-ceramic product.
[0004] The technical solution adopted by the present application to solve the technical problem is:
[0005] (1). A glass-ceramic product, which comprises, by weight percentage: SiO2: 40-55%; Al2O3: 15-30%; Li2O: 0.1-6%; ZnO: 9-20%; MgO: 0.1-6%; TiO2: 0.5-7%.
[0006] (2). The glass-ceramic product according to (1), which further comprises, by weight percentage: P2O5+ZrO2: 0-8%; and / or Na2O: 0-6%; and / or B2O3: 0-4%; and / or K2O: 0-3%; and / or CaO+BaO+SrO: 0-5%; and / or Y2O3: 0-6%; and / or fining agent: 0-2%.
[0007] (3). A glass-ceramic product, which comprises SiO2, Al2O3, ZnO and TiO2, and contains spinel crystal phase, and the drop resistance of the glass-ceramic product is 1200 mm or more.
[0008] (4). A glass-ceramic product, which contains spinel crystal phase, and the drop ball test height of the glass-ceramic product is 1000 mm or more.
[0009] (5). A glass-ceramic article comprising SiO2, Al2O3, Li2O, ZnO and TiO2, the glass-ceramic article having a crush strength of 400 N or more.
[0010] (6). A glass-ceramic article comprising SiO2, Al2O3, Li2O, ZnO and TiO2, the glass-ceramic article having a haze of 0.3% or less for a thickness of 1 mm or less.
[0011] (7). A glass-ceramic article comprising a spinel crystal phase, the glass-ceramic article having an average light ∣B∣ value of 1.0 or less for a thickness of 1 mm or less in the range of 400 to 800 nm.
[0012] (8). A glass-ceramic article comprising SiO2, Al2O3, Li2O, ZnO and TiO2, the glass-ceramic article having a surface stress of 200 MPa or more.
[0013] (9). A glass-ceramic article comprising SiO2, Al2O3, Li2O, ZnO and TiO2, the glass-ceramic article having a grain size of 60 nm or less.
[0014] (10). A glass-ceramic article comprising a spinel crystal phase, the glass-ceramic article having an ion exchange layer depth of 75 μm or more.
[0015] (11). A glass-ceramic article comprising a spinel crystal phase, the glass-ceramic article having a light transmittance of 87.0% or more at a wavelength of 550 nm for a thickness of 1 mm or less.
[0016] (12). A glass-ceramic article comprising SiO2, Al2O3 and ZnO, and comprising a spinel crystal phase.
[0017] (13). A glass-ceramic article comprising SiO2, Al2O3, Li2O and ZnO, the glass-ceramic article having a Vickers hardness of 650 kgf / mm 2 or more.
[0018] (14). The glass-ceramic article according to any one of (3) to (13), the components of which comprise, by weight percentage: SiO2: 40 to 55%; and / or Al2O3: 15 to 30%; and / or Li2O: 0.1 to 6%; and / or ZnO: 9 to 20%; and / or MgO: 0.1 to 6%; and / or TiO2: 0.5 to 7%; and / or P2O5 + ZrO2: 0 to 8%; and / or Na2O: 0 to 6%; and / or B2O3: 0 to 4%; and / or K2O: 0 to 3%; and / or CaO + BaO + SrO: 0 to 5%; and / or Y2O3: 0 to 6%; and / or fining agent: 0 to 2%.
[0019] (15). A glass-ceramic article, the composition of which, expressed in percent by weight, consists of: Si02: 40-55%; AI2O3: 15-30%; Li20: 0.1-6%; ZnO: 9-20%; MgO: 0.1-6%; Ti02: 0.5-7%; P205+Zr02: 0-8%; Na20: 0-6%; B203: 0-4%; K20: 0-3%; CaO+BaO+SrO: 0-5%; Y203: 0-6%; fining agent: 0-2%.
[0020] (16). The glass-ceramic article according to any one of (1) to (15), the composition of which, expressed in percent by weight, fulfils one or more of the following seven conditions:
[0021] 1) Li20 / Ti02 is 0.2-4.5, preferably Li20 / Ti02 is 0.5-3.5, more preferably Li20 / Ti02 is 0.7-2.5, further preferably Li20 / Ti02 is 0.75-1.5;
[0022] 2) AI2O3+ZnO is 26-45%, preferably AI2O3+ZnO is 30-42%, more preferably AI2O3+ZnO is 32-42%, further preferably AI2O3+ZnO is 35-40%;
[0023] 3) AI2O3 / ZnO is 1.0-3.0, preferably AI2O3 / ZnO is 1.2-2.8, more preferably AI2O3 / ZnO is 1.25-2.5, further preferably AI2O3 / ZnO is 1.5-2.3;
[0024] 4) Si02 / AI2O3 is 1.5-3.2, preferably Si02 / AI2O3 is 1.7-3.0, more preferably Si02 / AI2O3 is 1.8-2.8, further preferably Si02 / AI2O3 is 2.0-2.5;
[0025] 5) (Ti02+ZnO) / AI2O3 is 0.4-1.5, preferably (Ti02+ZnO) / AI2O3 is 0.5-1.2, more preferably (Ti02+ZnO) / AI2O3 is 0.6-1.0, further preferably (Ti02+ZnO) / AI2O3 is 0.6-0.9;
[0026] 6) (Li20+MgO) / Ti02 is 0.3-8.0, preferably (Li20+MgO) / Ti02 is 0.5-5.0, more preferably (Li20+MgO) / Ti02 is 1.0-3.0, further preferably (Li20+MgO) / Ti02 is 1.2-2.5;
[0027] 7) Al203 / (MgO + Ti02) is 1.3 to 10.0, preferably Al203 / (MgO + Ti02) is 1.5 to 8.0, more preferably Al203 / (MgO + Ti02) is 2.5 to 6.5, further preferably Al203 / (MgO + Ti02) is 3.0 to 5.5.
[0028] (17). The glass-ceramic article according to any one of (1) to (15), having components expressed in weight percentage satisfying one or more of the following four conditions:
[0029] 1) (Al203+ Li20) / P205is 5.0 to 45.0, preferably (Al203+ Li20) / P205is 7.0 to 35.0, more preferably (Al203+ Li20) / P205is 8.0 to 30.0, further preferably (Al203+ Li20) / P205is 10.0 to 25.0;
[0030] 2) P205 / Zr02is 0.1 to 5.0, preferably P205 / Zr02is 0.2 to 3.0, more preferably P205 / Zr02is 0.5 to 2.0, further preferably P205 / Zr02is 0.6 to 1.5;
[0031] 3) (Si02+ Na20) / ZnO is 2.2 to 6.2, preferably (Si02+ Na20) / ZnO is 2.5 to 6.0, more preferably (Si02+ Na20) / ZnO is 2.8 to 5.5, further preferably (Si02+ Na20) / ZnO is 3.0 to 5.0;
[0032] 4) (Na20 + K20) / ZnO is 0.8 or less, preferably (Na20 + K20) / ZnO is 0.6 or less, more preferably (Na20 + K20) / ZnO is 0.4 or less, further preferably (Na20 + K20) / ZnO is 0.2 or less.
[0033] (18). The glass-ceramic article according to any one of (1) to (15), comprising, in percent by weight: Si02: 45 to 53%, preferably Si02: 48 to 52%; and / or AI2O3: 18 to 25%, preferably AI2O3: 20 to 23%; and / or Li20: 1 to 5%, preferably Li20: 2 to 4%; and / or ZnO: 11 to 18%, preferably ZnO: 12 to 16%; and / or MgO: 1 to 5%, preferably MgO: 2 to 4%; and / or Ti02: 1 to 6%, preferably Ti02: 2 to 5%; and / or P205+Zr02: 0.1 to 7%, preferably P205+Zr02: 0.5 to 5%; and / or Na20: 0 to 4%, preferably Na20: 0 to 2%; and / or B203: 0 to 2%, preferably B203: 0 to 1%; and / or K20: 0 to 2%, preferably K20: 0 to 1%; and / or CaO+BaO+SrO: 0 to 4%, preferably CaO+BaO+SrO: 0 to 2%; and / or Y203: 0 to 4%, preferably Y203: 0 to 2%; and / or fining agent: 0 to 1%, preferably fining agent: 0 to 0.5%.
[0034] (19). The glass-ceramic article according to any one of (1) to (15), comprising, in percent by weight: P205: 0 to 5%, preferably P205: 0.5 to 4%, more preferably P205: 1 to 3%; and / or Zr02: 0 to 5%, preferably Zr02: 0.5 to 4%, more preferably Zr02: 1 to 3%.
[0035] (20). The glass-ceramic article according to any one of (1) to (15), comprising a spinel crystalline phase, preferably the spinel crystalline phase has a higher weight percentage than other crystalline phases, more preferably the spinel crystalline phase has a weight percentage of 20 to 60% of the glass-ceramic article, further preferably the spinel crystalline phase has a weight percentage of 25 to 50% of the glass-ceramic article, more further preferably the spinel crystalline phase has a weight percentage of 25 to 45% of the glass-ceramic article, and again further preferably the spinel crystalline phase has a weight percentage of 30 to 45% of the glass-ceramic article.
[0036] (21). The glass-ceramic article according to any one of (1) to (15), comprising a quartz crystalline phase, preferably the quartz crystalline phase has a weight percentage of 20% or less of the glass-ceramic article, more preferably the quartz crystalline phase has a weight percentage of 10% or less of the glass-ceramic article, further preferably the quartz crystalline phase has a weight percentage of 5% or less of the glass-ceramic article, and more further preferably the glass-ceramic article does not contain the quartz crystalline phase.
[0037] (22). The glass-ceramic article according to any one of (1) to (14), comprising, in percent by weight: La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0 to 5%, preferably La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0 to 2%, more preferably La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0 to 1%, further preferably free of La2O3, and / or free of Gd2O3, and / or free of Yb2O3, and / or free of Nb2O5, and / or free of WO3, and / or free of Bi2O3, and / or free of Ta2O5, and / or free of TeO2.
[0038] (23). The glass-ceramic article according to any one of (1) to (15), having a grain size of 60 nm or less, preferably 45 nm or less, more preferably 10 to 30 nm; and / or an ion exchange layer depth of 75 μm or more, preferably 80 to 150 μm, more preferably 100 to 125 μm; and / or a surface stress of 200 MPa or more, preferably 250 to 400 MPa, more preferably 300 to 400 MPa; and / or a drop ball test height of 1000 mm or more, preferably 1200 mm or more, more preferably 1500 mm or more; and / or a drop resistance of 1200 mm or more, preferably 1300 mm or more, more preferably 1400 mm or more; and / or a fracture toughness of 1.0 MPa-m½or more, preferably 1.2 MPa-m½or more, more preferably 1.2 to 1.6 MPa-m½; and / or a four-point bending strength of 500 MPa or more, preferably 600 MPa or more, more preferably 700 to 1000 MPa; and / or a crush strength of 400 N or more, preferably 400 to 550 N, more preferably 450 to 550 N; and / or a Vickers hardness of 650 kgf / mm2or more, preferably 660 kgf / mm2or more, more preferably 680 to 750 kgf / mm2. 1 / 2 , preferably 1.2 MPa-m½or more, more preferably 1.2 to 1.6 MPa-m½. 1 / 2 , preferably 1.2 MPa-m½or more, more preferably 1.2 to 1.6 MPa-m½. 1 / 2 ; and / or a four-point bending strength of 500 MPa or more, preferably 600 MPa or more, more preferably 700 to 1000 MPa; and / or a crush strength of 400 N or more, preferably 400 to 550 N, more preferably 450 to 550 N; and / or a Vickers hardness of 650 kgf / mm2or more, preferably 660 kgf / mm2or more, more preferably 680 to 750 kgf / mm2. 2 , preferably 1.2 MPa-m½or more, more preferably 1.2 to 1.6 MPa-m½. 2 , preferably 1.2 MPa-m½or more, more preferably 1.2 to 1.6 MPa-m½. 2 .
[0039] (24). The glass-ceramic article according to any one of (1) to (15), the glass-ceramic article having a thickness of 1 mm or less, a haze of 0.3% or less, preferably 0.25% or less, more preferably 0.05 to 0.2%; and / or an average light transmittance of 87.0% or more, preferably 88.5% or more, more preferably 89.5% or more, in the wavelength range of 400 to 800 nm; and / or a light transmittance of 87.0% or more, preferably 88.0% or more, more preferably 89.0% or more, at a wavelength of 550 nm; and / or an average light |B| value of 1.0 or less, preferably 0.8 or less, more preferably 0.3 to 0.6, in the wavelength range of 400 to 800 nm.
[0040] (25). The glass-ceramic article according to (24), the glass-ceramic article having a thickness of 0.2 to 1 mm, preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, further preferably 0.55 mm or 0.6 mm or 0.68 mm or 0.7 mm or 0.75 mm.
[0041] (26). The glass-ceramic article according to any one of (1) to (14), the glass-ceramic article comprising, in terms of weight percentage: NiO: 0 to 4%; and / or Ni2O3: 0 to 4%; and / or CoO: 0 to 2%; and / or Co2O3: 0 to 2%; and / or Fe2O3: 0 to 7%; and / or MnO2: 0 to 4%; and / or Er2O3: 0 to 8%; and / or Nd2O3: 0 to 8%; and / or Cu2O: 0 to 4%; and / or Pr2O3: 0 to 8%; and / or CeO2: 0 to 4%.
[0042] (27). The glass-ceramic article according to any one of (1) to (14), the glass-ceramic article comprising, in terms of weight percentage: NiO: 0.1 to 4%; and / or Ni2O3: 0.1 to 4%; and / or CoO: 0.05 to 2%; and / or Co2O3: 0.05 to 2%; and / or Fe2O3: 0.2 to 7%; and / or MnO2: 0.1 to 4%; and / or Er2O3: 0.4 to 8%; and / or Nd2O3: 0.4 to 8%; and / or Cu2O: 0.5 to 4%; and / or Pr2O3: 0.4 to 8%; and / or CeO2: 0.5 to 4%.
[0043] (28). The glass-ceramic article according to any one of (1) to (14), comprising, in percent by weight: NiO: 0.1 to 3%; and / or Ni2O3: 0.1 to 3%; and / or CoO: 0.05 to 1.8%; and / or Co2O3: 0.05 to 1.8%; and / or Fe2O3: 0.2 to 5%; and / or MnO2: 0.1 to 3%; and / or Er2O3: 0.4 to 6%; and / or Nd2O3: 0.4 to 6%; and / or Cu2O: 0.5 to 3%; and / or Pr2O3: 0.4 to 6%; and / or CeO2: 0.5 to 3%.
[0044] (29). The glass-ceramic article according to any one of (1) to (14), comprising, in percent by weight: NiO: 0.1 to 3%; and / or Ni2O3: 0.1 to 3%.
[0045] (30). The glass-ceramic article according to any one of (1) to (14), comprising, in percent by weight: CoO: 0.05 to 1.8%; and / or Co2O3: 0.05 to 1.8%.
[0046] (31). The glass-ceramic article according to any one of (1) to (14), comprising, in percent by weight: Cu2O: 0.5 to 3%; and / or CeO2: 0.5 to 3%.
[0047] (32). The glass-ceramic article according to any one of (1) to (14), comprising, in percent by weight: Fe2O3: 0.2 to 5%, CoO: 0.05 to 0.3%; or Fe2O3: 0.2 to 5%, Co2O3: 0.05 to 0.3%; or Fe2O3: 0.2 to 5%, CoO: 0.05 to 0.3%, NiO: 0.1 to 1%; or Fe2O3: 0.2 to 5%, Co2O3: 0.05 to 0.3%, NiO: 0.1 to 1%.
[0048] (33). The glass-ceramic article according to any one of (1) to (14), comprising, in percent by weight: Pr2O3: 0.4 to 6%; or Fe2O3: 0.2 to 5%; or MnO2: 0.1 to 3%; or Er2O3: 0.4 to 6%; or Nd2O3: 0.4 to 6%.
[0049] (34). The glass-ceramic article according to any one of (1) to (14), comprising, in percent by weight: Er2O3: 0.4 to 6%, Nd2O3: 0.4 to 4%, MnO2: 0.1 to 2%.
[0050] (35). A glass-ceramic comprising, in percent by weight: SiO2: 40 to 55%; Al2O3: 15 to 30%; Li2O: 0.1 to 6%; ZnO: 9 to 20%; MgO: 0.1 to 6%; and TiO2: 0.5 to 7%.
[0051] (36). The glass-ceramic according to (35), further comprising, in percent by weight: P2O5 + ZrO2: 0 to 8%; and / or Na2O: 0 to 6%; and / or B2O3: 0 to 4%; and / or K2O: 0 to 3%; and / or CaO + BaO + SrO: 0 to 5%; and / or Y2O3: 0 to 6%; and / or fining agent: 0 to 2%.
[0052] (37). A glass-ceramic comprising SiO2, Al2O3, ZnO and TiO2, the glass-ceramic comprising spinel crystal phase, the glass-ceramic having a Vickers hardness of 550 kgf / mm 2 above.
[0053] (38). A glass-ceramic comprising SiO2, Al2O3, Li2O, ZnO and TiO2, the glass-ceramic comprising spinel crystal phase.
[0054] (39). A glass-ceramic comprising spinel crystal phase, the glass-ceramic having a grain size of 60 nm or less.
[0055] (40). A glass-ceramic comprising SiO2, Al2O3, Li2O, ZnO and TiO2, the glass-ceramic having a haze of 0.3% or less for a thickness of 1 mm or less.
[0056] (41). A glass-ceramic comprising spinel crystal phase, the glass-ceramic having a light transmittance of 87.0% or more at a wavelength of 550 nm for a thickness of 1 mm or less.
[0057] (42). A glass-ceramic comprising SiO2, Al2O3, Li2O, ZnO and TiO2, the glass-ceramic having a Young's modulus of 80 to 110 GPa.
[0058] (43). A glass-ceramic comprising SiO2, Al2O3, Li2O and ZnO, the glass-ceramic having an average light ∣B∣ value of 1.0 or less for a thickness of 1 mm or less at a wavelength of 400 to 800 nm.
[0059] (44). A glass-ceramic comprising SiO2, Al2O3 and ZnO, the glass-ceramic having an average light transmittance of 87.0% or more for a thickness of 1 mm or less at a wavelength of 400 to 800 nm.
[0060] (45). The glass-ceramic according to any one of (37) to (44), comprising, expressed in percentage by weight: SiO2: 40 to 55%; and / or Al2O3: 15 to 30%; and / or Li2O: 0.1 to 6%; and / or ZnO: 9 to 20%; and / or MgO: 0.1 to 6%; and / or TiO2: 0.5 to 7%; and / or P2O5+ZrO2: 0 to 8%; and / or Na2O: 0 to 6%; and / or B2O3: 0 to 4%; and / or K2O: 0 to 3%; and / or CaO+BaO+SrO: 0 to 5%; and / or Y2O3: 0 to 6%; and / or fining agent: 0 to 2%.
[0061] (46). A glass-ceramic, comprising, expressed in percentage by weight: SiO2: 40 to 55%; Al2O3: 15 to 30%; Li2O: 0.1 to 6%; ZnO: 9 to 20%; MgO: 0.1 to 6%; TiO2: 0.5 to 7%; P2O5+ZrO2: 0 to 8%; Na2O: 0 to 6%; B2O3: 0 to 4%; K2O: 0 to 3%; CaO+BaO+SrO: 0 to 5%; Y2O3: 0 to 6%; fining agent: 0 to 2%.
[0062] (47). The glass-ceramic according to any one of (35) to (46), comprising, expressed in percentage by weight, one or more of the following seven cases:
[0063] 1) Li2O / TiO2 is 0.2 to 4.5, preferably Li2O / TiO2 is 0.5 to 3.5, more preferably Li2O / TiO2 is 0.7 to 2.5, further preferably Li2O / TiO2 is 0.75 to 1.5;
[0064] 2) Al2O3+ZnO is 26 to 45%, preferably Al2O3+ZnO is 30 to 42%, more preferably Al2O3+ZnO is 32 to 42%, further preferably Al2O3+ZnO is 35 to 40%;
[0065] 3) Al2O3 / ZnO is 1.0 to 3.0, preferably Al2O3 / ZnO is 1.2 to 2.8, more preferably Al2O3 / ZnO is 1.25 to 2.5, further preferably Al2O3 / ZnO is 1.5 to 2.3;
[0066] 4) SiO2 / Al2O3 is 1.5 to 3.2, preferably SiO2 / Al2O3 is 1.7 to 3.0, more preferably SiO2 / Al2O3 is 1.8 to 2.8, further preferably SiO2 / Al2O3 is 2.0 to 2.5;
[0067] 5) (TiO2+ZnO) / Al2O3 is 0.4 to 1.5, preferably (TiO2+ZnO) / Al2O3 is 0.5 to 1.2, more preferably (TiO2+ZnO) / Al2O3 is 0.6 to 1.0, further preferably (TiO2+ZnO) / Al2O3 is 0.6 to 0.9;
[0068] 6) (Li2O+MgO) / TiO2 is 0.3 to 8.0, preferably (Li2O+MgO) / TiO2 is 0.5 to 5.0, more preferably (Li2O+MgO) / TiO2 is 1.0 to 3.0, further preferably (Li2O+MgO) / TiO2 is 1.2 to 2.5;
[0069] 7) Al2O3 / (MgO+TiO2) is 1.3 to 10.0, preferably Al2O3 / (MgO+TiO2) is 1.5 to 8.0, more preferably Al2O3 / (MgO+TiO2) is 2.5 to 6.5, further preferably Al2O3 / (MgO+TiO2) is 3.0 to 5.5.
[0070] (48). The glass-ceramic according to any one of (35) to (46), the components of which, expressed as a percentage by weight, satisfy one or more of the following four cases:
[0071] 1) (Al2O3+Li2O) / P2O5 is 5.0 to 45.0, preferably (Al2O3+Li2O) / P2O5 is 7.0 to 35.0, more preferably (Al2O3+Li2O) / P2O5 is 8.0 to 30.0, further preferably (Al2O3+Li2O) / P2O5 is 10.0 to 25.0;
[0072] 2) P2O5 / ZrO2 is 0.1 to 5.0, preferably P2O5 / ZrO2 is 0.2 to 3.0, more preferably P2O5 / ZrO2 is 0.5 to 2.0, further preferably P2O5 / ZrO2 is 0.6 to 1.5;
[0073] 3) (SiO2+Na2O) / ZnO is 2.2 to 6.2, preferably (SiO2+Na2O) / ZnO is 2.5 to 6.0, more preferably (SiO2+Na2O) / ZnO is 2.8 to 5.5, further preferably (SiO2+Na2O) / ZnO is 3.0 to 5.0;
[0074] 4) (Na2O+K2O) / ZnO is 0.8 or less, preferably (Na2O+K2O) / ZnO is 0.6 or less, more preferably (Na2O+K2O) / ZnO is 0.4 or less, further preferably (Na2O+K2O) / ZnO is 0.2 or less.
[0075] (49). The glass-ceramic according to any one of (35) to (46), comprising, expressed in percentage by weight: SiO2: 45 to 53%, preferably SiO2: 48 to 52%; and / or Al2O3: 18 to 25%, preferably Al2O3: 20 to 23%; and / or Li2O: 1 to 5%, preferably Li2O: 2 to 4%; and / or ZnO: 11 to 18%, preferably ZnO: 12 to 16%; and / or MgO: 1 to 5%, preferably MgO: 2 to 4%; and / or TiO2: 1 to 6%, preferably TiO2: 2 to 5%; and / or P2O5+ZrO2: 0.1 to 7%, preferably P2O5+ZrO2: 0.5 to 5%; and / or Na2O: 0 to 4%, preferably Na2O: 0 to 2%; and / or B2O3: 0 to 2%, preferably B2O3: 0 to 1%; and / or K2O: 0 to 2%, preferably K2O: 0 to 1%; and / or CaO+BaO+SrO: 0 to 4%, preferably CaO+BaO+SrO: 0 to 2%; and / or Y2O3: 0 to 4%, preferably Y2O3: 0 to 2%; and / or fining agent: 0 to 1%, preferably fining agent: 0 to 0.5%.
[0076] (50). The glass-ceramic according to any one of (35) to (46), comprising, expressed in percentage by weight: P2O5: 0 to 5%, preferably P2O5: 0.5 to 4%, more preferably P2O5: 1 to 3%; and / or ZrO2: 0 to 5%, preferably ZrO2: 0.5 to 4%, more preferably ZrO2: 1 to 3%.
[0077] (51). The glass-ceramic according to any one of (35) to (46), comprising a spinel crystalline phase, preferably the spinel crystalline phase has a higher percentage by weight than other crystalline phases, more preferably the spinel crystalline phase has a percentage by weight of the glass-ceramic of 20 to 60%, further preferably the spinel crystalline phase has a percentage by weight of the glass-ceramic of 25 to 50%, more further preferably the spinel crystalline phase has a percentage by weight of the glass-ceramic of 25 to 45%, still further preferably the spinel crystalline phase has a percentage by weight of the glass-ceramic of 30 to 45%.
[0078] (52). The glass-ceramic according to any one of (35) to (46), comprising a quartz crystalline phase, preferably the quartz crystalline phase has a percentage by weight of the glass-ceramic of 20% or less, more preferably the quartz crystalline phase has a percentage by weight of the glass-ceramic of 10% or less, further preferably the quartz crystalline phase has a percentage by weight of the glass-ceramic of 5% or less, more further preferably the glass-ceramic does not contain a quartz crystalline phase.
[0079] (53). The glass-ceramic according to any one of (35) to (45), comprising, in percent by weight: La2O3+ Gd2O3+ Yb2O3+ Nb2O5+ WO3+ Bi2O3+ Ta2O5+ TeO2: 0 to 5%, preferably La2O3+ Gd2O3+ Yb2O3+ Nb2O5+ WO3+ Bi2O3+ Ta2O5+ TeO2: 0 to 2%, more preferably La2O3+ Gd2O3+ Yb2O3+ Nb2O5+ WO3+ Bi2O3+ Ta2O5+ TeO2: 0 to 1%, further preferably free of La2O3, and / or free of Gd2O3, and / or free of Yb2O3, and / or free of Nb2O5, and / or free of WO3, and / or free of Bi2O3, and / or free of Ta2O5, and / or free of TeO2.
[0080] (54). The glass-ceramic according to any one of (35) to (46), having a grain size of 60 nm or less, preferably 45 nm or less, more preferably 10 to 30 nm; and / or a Young's modulus of 80 to 110 GPa, preferably 85 to 105 GPa, more preferably 90 to 105 GPa; and / or a Vickers hardness of 550 kgf / mm 2 preferably 580 kgf / mm 2 more preferably 600 to 650 kgf / mm 2 .
[0081] (55). The glass-ceramic according to any one of (35) to (46), having a haze of 0.3% or less, preferably 0.25% or less, more preferably 0.05 to 0.2%, for a thickness of 1 mm or less; and / or an average light transmittance of 87.0% or more, preferably 88.5% or more, more preferably 89.5% or more, for a wavelength of 400 to 800 nm; and / or a light transmittance of 87.0% or more, preferably 88.0% or more, more preferably 89.0% or more, for a wavelength of 550 nm; and / or an average light ∣B∣ value of 1.0 or less, preferably 0.8 or less, more preferably 0.3 to 0.6, for a wavelength of 400 to 800 nm.
[0082] (56). The glass-ceramic according to (55), having a thickness of 0.2 to 1 mm, preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, further preferably 0.55 mm or 0.6 mm or 0.68 mm or 0.7 mm or 0.75 mm.
[0083] (57). The glass-ceramic according to any one of (35) to (45), comprising, expressed in percentage by weight: NiO: 0 to 4%; and / or Ni2O3: 0 to 4%; and / or CoO: 0 to 2%; and / or Co2O3: 0 to 2%; and / or Fe2O3: 0 to 7%; and / or MnO2: 0 to 4%; and / or Er2O3: 0 to 8%; and / or Nd2O3: 0 to 8%; and / or Cu2O: 0 to 4%; and / or Pr2O3: 0 to 8%; and / or CeO2: 0 to 4%.
[0084] (58). The glass-ceramic according to any one of (35) to (45), comprising, expressed in percentage by weight: NiO: 0.1 to 4%; and / or Ni2O3: 0.1 to 4%; and / or CoO: 0.05 to 2%; and / or Co2O3: 0.05 to 2%; and / or Fe2O3: 0.2 to 7%; and / or MnO2: 0.1 to 4%; and / or Er2O3: 0.4 to 8%; and / or Nd2O3: 0.4 to 8%; and / or Cu2O: 0.5 to 4%; and / or Pr2O3: 0.4 to 8%; and / or CeO2: 0.5 to 4%.
[0085] (59). The glass-ceramic according to any one of (35) to (45), comprising, expressed in percentage by weight: NiO: 0.1 to 3%; and / or Ni2O3: 0.1 to 3%; and / or CoO: 0.05 to 1.8%; and / or Co2O3: 0.05 to 1.8%; and / or Fe2O3: 0.2 to 5%; and / or MnO2: 0.1 to 3%; and / or Er2O3: 0.4 to 6%; and / or Nd2O3: 0.4 to 6%; and / or Cu2O: 0.5 to 3%; and / or Pr2O3: 0.4 to 6%; and / or CeO2: 0.5 to 3%.
[0086] (60). The glass-ceramic according to any one of (35) to (45), comprising, expressed in percentage by weight: NiO: 0.1 to 3%; and / or Ni2O3: 0.1 to 3%.
[0087] (61). The glass-ceramic according to any one of (35) to (45), comprising, expressed in percentage by weight: CoO: 0.05 to 1.8%; and / or Co2O3: 0.05 to 1.8%.
[0088] (62). The glass-ceramic according to any one of (35) to (45), comprising, expressed in percentage by weight: Cu2O: 0.5 to 3%; and / or CeO2: 0.5 to 3%.
[0089] (63). The glass-ceramic according to any one of (35) to (45), comprising, in percent by weight: Fe203: 0.2 to 5%, CoO: 0.05 to 0.3%; or Fe203: 0.2 to 5%, Co203: 0.05 to 0.3%; or Fe203: 0.2 to 5%, CoO: 0.05 to 0.3%, NiO: 0.1 to 1%; or Fe203: 0.2 to 5%, Co203: 0.05 to 0.3%, NiO: 0.1 to 1%.
[0090] (64). The glass-ceramic according to any one of (35) to (45), comprising, in percent by weight: Pr203: 0.4 to 6%; or Fe203: 0.2 to 5%; or Mn02: 0.1 to 3%; or Er203: 0.4 to 6%; or Nd203: 0.4 to 6%.
[0091] (65). The glass-ceramic according to any one of (35) to (45), comprising, in percent by weight: Er203: 0.4 to 6%, Nd203: 0.4 to 4%, Mn02: 0.1 to 2%.
[0092] (66). A glass-ceramic shaped body comprising the glass-ceramic according to any one of (35) to (65).
[0093] (67). A glass cover plate comprising the glass-ceramic article according to any one of (1) to (34), and / or the glass-ceramic according to any one of (35) to (65), and / or the glass-ceramic shaped body according to (66).
[0094] (68). A glass component comprising the glass-ceramic article according to any one of (1) to (34), and / or the glass-ceramic according to any one of (35) to (65), and / or the glass-ceramic shaped body according to (66).
[0095] (69). An electronic device comprising the glass-ceramic article according to any one of (1) to (34), and / or the glass-ceramic according to any one of (35) to (65), and / or the glass-ceramic shaped body according to (66), and / or the glass cover plate according to (67), and / or the glass component according to (68).
[0096] (70). A display device comprising the glass-ceramic article according to any one of (1) to (34), and / or the glass-ceramic according to any one of (35) to (65), and / or the glass-ceramic shaped body according to (66), and / or the glass cover plate according to (67), and / or the glass component according to (68).
[0097] (71). A method of making the glass-ceramic article of any one of (1) to (34), the method comprising the steps of: forming a base glass, crystallizing the base glass to form the glass-ceramic, and then forming the glass-ceramic article by a chemical strengthening process.
[0098] (72). The method of making the glass-ceramic article of (71), the forming of the base glass comprising the steps of: mixing raw materials in a predetermined ratio, melting the mixture in an electric or gas furnace at a temperature ranging from 1350 to 1550 °C for 5 to 24 hours, preferably at a temperature ranging from 1450 to 1550 °C, and then obtaining the base glass by subjecting the molten mixture to refining, homogenizing, shaping, and annealing, wherein the refining temperature is greater than 1550 °C but less than or equal to 1650 °C, and the annealing temperature is 450 to 600 °C.
[0099] (73). The method of making the glass-ceramic article of (71), the crystallizing process comprising the steps of: increasing the temperature to a predetermined crystallization temperature, maintaining the temperature at the crystallization temperature for a predetermined time period, and then decreasing the temperature, wherein the crystallization temperature is 600 to 800 °C, preferably 650 to 750 °C, and the time period for maintaining the temperature at the crystallization temperature is 1 to 10 hours, preferably 3 to 6 hours.
[0100] (74). The method of making the glass-ceramic article of (71), the crystallizing process comprising the steps of: performing a nucleation process at a first temperature, and then performing a crystal growth process at a second temperature.
[0101] (75). The method of making the glass-ceramic article of (74), the crystallizing process comprising: the first temperature is 600 to 700 °C, the second temperature is greater than 700 °C but less than or equal to 800 °C, the time period for maintaining the temperature at the first temperature is 1 to 6 hours, and the time period for maintaining the temperature at the second temperature is 2 to 5 hours.
[0102] (76). The method of making the glass-ceramic article of (71), the chemical strengthening process comprising: immersing the glass-ceramic in a molten Na salt bath at a temperature of 350 to 470 °C for 1 to 36 hours, preferably at a temperature of 400 to 460 °C for 2 to 15 hours; and / or immersing the glass-ceramic in a mixed bath of molten K and Na salts at a temperature of 360 to 450 °C for 1 to 36 hours, preferably for 2 to 24 hours.
[0103] (77). The method of making the glass-ceramic of any one of (35) to (65), the method comprising the steps of: forming a base glass, and then crystallizing the base glass to form the glass-ceramic.
[0104] (78). The method of manufacturing the glass-ceramic according to (77), wherein the forming of the matrix glass comprises the following steps: mixing raw materials in a certain proportion, then putting them into a crucible, melting at a temperature ranging from 1350 to 1550 °C for 5 to 24 hours in an electric furnace or gas furnace, preferably the melting temperature is from 1450 to 1550 °C, then obtaining the matrix glass after refining, homogenizing, forming and annealing, wherein the refining temperature is greater than 1550 °C but less than or equal to 1650 °C, and the annealing temperature is from 450 to 600 °C.
[0105] (79). The method of manufacturing the glass-ceramic according to (77), wherein the crystallization process comprises the following steps: increasing the temperature to a specified crystallization treatment temperature, keeping the temperature for a certain time after reaching the crystallization treatment temperature, and then decreasing the temperature, wherein the crystallization treatment temperature is from 600 to 800 °C, preferably from 650 to 750 °C, and the keeping time at the crystallization treatment temperature is from 1 to 10 hours, preferably from 3 to 6 hours.
[0106] (80). The method of manufacturing the glass-ceramic product according to (77), wherein the crystallization process comprises the following steps: performing a nucleation process at a first temperature, and then performing a crystal growth process at a second temperature.
[0107] (81). The method of manufacturing the glass-ceramic product according to (80), wherein the crystallization process comprises: the first temperature is from 600 to 700 °C, the second temperature is greater than 700 °C but less than or equal to 800 °C, the keeping time at the first temperature is from 1 to 6 hours, and the keeping time at the second temperature is from 2 to 5 hours.
[0108] (82). The method of manufacturing the glass-ceramic shaped body according to (66), wherein the method comprises grinding or polishing the glass-ceramic to obtain the glass-ceramic shaped body, or performing a hot bending process or a press forming process on the matrix glass or the glass-ceramic at a certain temperature to obtain the glass-ceramic shaped body.
[0109] (83). The method of manufacturing the glass-ceramic shaped body according to (82), wherein the method comprises the following steps: performing a primary crystallization heat treatment process on the matrix glass, including increasing the temperature, keeping the temperature for nucleation, increasing the temperature, keeping the temperature for crystallization, and decreasing the temperature to room temperature to form a pre-crystallized glass; and performing a hot working process on the pre-crystallized glass to obtain the glass-ceramic shaped body.
[0110] (84). The method of manufacturing the glass-ceramic shaped body according to (82), wherein the method comprises the following steps:
[0111] 1) Temperature rising preheating: the base glass or pre-crystallized glass or glass-ceramics is placed in the mold, the mold is sequentially passed through each temperature rising station in the thermal bending machine, and stays at each station for a certain time for heat preservation, the preheating zone temperature is 400-800℃, the pressure is 0.01-0.05MPa, and the time is 40-200s;
[0112] 2) Pressure forming: after preheating, the mold is transferred to the forming station, the thermal bending machine applies a certain pressure to the mold, the pressure range is 0.1-0.8Mpa, the forming station temperature range is 600-850℃, and the forming time range is 40-200s;
[0113] 3) Pressure holding and temperature dropping: the mold is transferred to the temperature dropping station and dropped station by station, the temperature dropping temperature range is 750-500℃, the pressure is 0.01-0.05Mpa, and the time is 40-200s.
[0114] The beneficial effects of the present application are: through reasonable component design, the glass-ceramics or glass-ceramics product obtained by the present application has excellent mechanical properties, and is suitable for display devices or electronic devices. DETAILED DESCRIPTION
[0115] The glass-ceramics and glass-ceramics product of the present application is a material having a crystalline phase (sometimes also referred to as crystal) and a glass phase. The crystalline phase of the glass-ceramics and glass-ceramics product can be distinguished and / or measured by the peak angle appearing in the X-ray diffraction pattern of X-ray diffraction analysis by TEMEDX.
[0116] The inventors of the present application have obtained the glass-ceramics or glass-ceramics product of the present application through repeated experiments and research on the specific components constituting the glass-ceramics and glass-ceramics product, by regulating the content and content ratio of the specific components to specific values and making them contain specific crystalline phases.
[0117] Hereinafter, the range of each component (ingredient) of the base glass, glass-ceramics and glass-ceramics product of the present application will be described. In the present specification, if not otherwise specified, the content of each component is expressed as a weight percentage (wt%) with respect to the total amount of the base glass or the glass-ceramics or the glass-ceramics product composition converted into oxides. Here, the "composition converted into oxides" refers to the case where the oxides, composite salts and hydroxides, etc. used as raw materials for the base glass, glass-ceramics or glass-ceramics product composition of the present application are decomposed and converted into oxides when melted, and the total amount of the oxides is taken as 100%. In addition, in the present specification, the base glass before crystallization (i.e. the crystallization process treatment) is referred to as glass, the base glass after crystallization (i.e. the crystallization process treatment) is referred to as glass-ceramics, and the glass-ceramics product refers to the product obtained after the glass-ceramics is chemically strengthened.
[0118] Unless otherwise indicated herein, the numerical values listed in this document are inclusive of the upper and lower limits, the terms "below" and "above" include the endpoints, and all integers and fractions within that range, unless otherwise indicated. As used herein, the term "about" means that the formula, parameters, and other quantities and characteristics are not, and need not be, exact, and allowances are to be made for tolerances, conversion factors, measurement error, and the like. As used herein, "and / or" is inclusive of the items that it connects, e.g., A; and / or B, means only A, or only B, or both A and B.
[0119] In some embodiments of the application, the crystalline phase in the glass-ceramic or glass-ceramic article comprises a spinel crystalline phase, preferably the spinel crystalline phase comprises a zinc aluminate spinel crystalline phase (ZnAl204). In some embodiments, the spinel crystalline phase has a higher weight percentage than other crystalline phases. In some embodiments, the spinel crystalline phase comprises 20-60% by weight of the glass-ceramic or glass-ceramic article, preferably the spinel crystalline phase comprises 25-50% by weight of the glass-ceramic or glass-ceramic article, more preferably the spinel crystalline phase comprises 25-45% by weight of the glass-ceramic or glass-ceramic article, even more preferably the spinel crystalline phase comprises 30-45% by weight of the glass-ceramic or glass-ceramic article. In some embodiments, the spinel crystalline phase comprises 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60% by weight of the glass-ceramic or glass-ceramic article.
[0120] In some embodiments of the present application, the crystalline phase in the glass-ceramics or glass-ceramic articles contains quartz crystalline phase (including both quartz and quartz solid solution), preferably, the quartz crystalline phase contains β-quartz solid solution. In some embodiments, the quartz crystalline phase accounts for 20% or less by weight of the glass-ceramics or glass-ceramic articles, preferably, the quartz crystalline phase accounts for 10% or less by weight of the glass-ceramics or glass-ceramic articles, more preferably, the quartz crystalline phase accounts for 5% or less by weight of the glass-ceramics or glass-ceramic articles. In some embodiments, it is further preferred that the glass-ceramics or glass-ceramic articles do not contain quartz crystalline phase. In some embodiments, the quartz crystalline phase accounts for 0%, more than 0%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20% by weight of the glass-ceramics or glass-ceramic articles.
[0121] SiO2is the network former of the glass-ceramics and glass-ceramic articles of the present application, which can form a network structure using the structural units of silicon-oxygen tetrahedron to form the basic structure of silicate. In some embodiments, SiO2is also a necessary component for forming quartz crystalline phase. If the content of SiO2is too low, the chemical stability of the glass-ceramics and glass-ceramic articles will be poor; if the content of SiO2is too high, the viscosity of the glass will be greatly increased, the melting temperature will be increased, the material melting will be difficult, and the forming of the matrix glass will be difficult. Therefore, the content of SiO2in the present application is 40-55%, preferably 45-53%, more preferably 48-52%. In some embodiments, the content of SiO2may be about 40%, 40.5%, 41%, 41.5%, 42%, 42.5%, 43%, 43.5%, 44%, 44.5%, 45%, 45.5%, 46%, 46.5%, 47%, 47.5%, 48%, 48.5%, 49%, 49.5%, 50%, 50.5%, 51%, 51.5%, 52%, 52.5%, 53%, 53.5%, 54%, 54.5%, 55%.
[0122] Al2O3is beneficial to improve the mechanical properties and chemical stability of the glass-ceramics and glass-ceramic articles of the present application, and is also a necessary component for forming spinel crystalline phase. Al2O3can form [AlO4] tetrahedron to replace part of [SiO4] tetrahedron to form a network structure. The molecular volume of [AlO4] tetrahedron is 41 cm3, which is smaller than that of [SiO4] tetrahedron (47 cm3), so the introduction of Al2O3can increase the density of the glass-ceramics and glass-ceramic articles. In some embodiments, the content of Al2O3is 0.1-5%, preferably 0.5-3%, more preferably 1-2% by weight of the glass-ceramics or glass-ceramic articles. In some embodiments, the content of Al2O3may be about 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5% by weight of the glass-ceramics or glass-ceramic articles. 3 / mol, the molecular volume of [SiO4] tetrahedron is 27.2 cm 3 / mol, the molecular volume of [SiO4] tetrahedron is 27.2 cm + , the promotion of ion exchange. Al2O3 content is too low, not conducive to the promotion of strengthening effect and the precipitation of crystal, the mechanical properties and chemical stability of glass are poor. Al2O3 content is too high, glass melting is difficult, the melting temperature is high, the surface is easy to precipitate stone during forming. Therefore, the content of Al2O3 is 15-30%, preferably 18-25%, more preferably 20-23%. In some embodiments, about 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, 30% of Al2O3 can be included.
[0123] In some embodiments, the ratio of SiO2 / Al2O3 between the content of SiO2 and the content of Al2O3 is controlled in the range of 1.5-3.2, which is conducive to improving the ball test height and four-point bending strength of the microcrystalline glass and the microcrystalline glass product, and improving the ion exchange layer depth and surface stress of the microcrystalline glass product. Therefore, SiO2 / Al2O3 is preferably 1.5-3.2, more preferably SiO2 / Al2O3 is 1.7-3.0, further preferably SiO2 / Al2O3 is 1.8-2.8, and more preferably SiO2 / Al2O3 is 2.0-2.5. In some embodiments, the value of SiO2 / Al2O3 is 1.5, 1.55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, 2.0, 2.05, 2.1, 2.15, 2.2, 2.25, 2.3, 2.35, 2.4, 2.45, 2.5, 2.55, 2.6, 2.65, 2.7, 2.75, 2.8, 2.85, 2.9, 2.95, 3.0, 3.05, 3.1, 3.15, 3.2.
[0124] Li2O can reduce the melting point of the glass, and is also a necessary component for participating in chemical strengthening and improving the mechanical properties of the glass-ceramic article. On the other hand, Li2O can provide free oxygen and reduce TiO2coloring. If the content of Li2O is too high, the crystals in the glass-ceramic and glass-ceramic article can easily grow, and the crystal growth is unstable, which can affect the transmittance of the glass-ceramic and glass-ceramic article and make the chemical stability worse. Therefore, the content of Li2O is 0.1-6%, preferably 1-5%, and more preferably 2-4%. In some embodiments, about 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6% of Li2O can be included.
[0125] ZnO is a necessary component for forming the spinel phase in the present application, and the content of the spinel phase can be controlled by controlling the content of ZnO and Al2O3, so as to ensure the mechanical strength and the transmittance. If the content of ZnO is low, the content of the crystal phase in the glass-ceramic and glass-ceramic article is low, and the mechanical properties such as Vickers hardness and Young's modulus are poor. If the content of ZnO is too high, the residual Zn 2+ in the glass phase hinders ion exchange in the chemical strengthening process, and is not conducive to obtaining a high-performance glass-ceramic article. Therefore, the content of ZnO is 9-20%, preferably 11-18%, and more preferably 12-16%. In some embodiments, about 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20% of ZnO can be included.
[0126] In some embodiments, the total content of Al2O3 and ZnO, Al2O3+ZnO, is controlled in the range of 26-45%, which is beneficial for the microcrystalline glass and the microcrystalline glass product to obtain a desired content of spinel crystal phase, to improve the drop resistance and the falling ball test height of the microcrystalline glass and the microcrystalline glass product, and to prevent the surface stress of the microcrystalline glass product from deteriorating. Therefore, Al2O3+ZnO is preferably 26-45%, more preferably Al2O3+ZnO is 30-42%, further preferably Al2O3+ZnO is 32-42%, and more further preferably Al2O3+ZnO is 35-40%. In some embodiments, Al2O3+ZnO is 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 32%, 32.5%, 33%, 33.5%, 34%, 34.5%, 35%, 35.5%, 36%, 36.5%, 37%, 37.5%, 38%, 38.5%, 39%, 39.5%, 40%, 40.5%, 41%, 41.5%, 42%, 42.5%, 43%, 43.5%, 44%, 44.5%, 45%.
[0127] In some embodiments, the ratio between the content of Al2O3 and the content of ZnO, Al2O3 / ZnO, is controlled in the range of 1.0-3.0, which is beneficial for improving the hardness of the microcrystalline glass and the microcrystalline glass product, optimizing the Young's modulus, and preventing the transmittance of the microcrystalline glass and the microcrystalline glass product from decreasing and the haze from deteriorating. Therefore, Al2O3 / ZnO is preferably 1.0-3.0, more preferably Al2O3 / ZnO is 1.2-2.8, further preferably Al2O3 / ZnO is 1.25-2.5, and more further preferably Al2O3 / ZnO is 1.5-2.3. In some embodiments, Al2O3 / ZnO is 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, 2.0, 2.05, 2.1, 2.15, 2.2, 2.25, 2.3, 2.35, 2.4, 2.45, 2.5, 2.55, 2.6, 2.65, 2.7, 2.75, 2.8, 2.85, 2.9, 2.95, 3.0.
[0128] TiO2 is the nucleating agent for the glass-ceramic and glass-ceramic products of this invention. If the TiO2 content is too high, it will cause severe coloration (brownish-yellow) in the glass-ceramic and glass-ceramic products, reducing the transmittance in the visible light region and increasing haze and |B| value. Furthermore, excessive TiO2 content can easily cause the glass to emulsify during molding and crystallization, making the glass opaque. Therefore, the TiO2 content in this invention is 0.5-7%, preferably 1-6%, and more preferably 2-5%. In some embodiments, it may contain about 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, or 7% TiO2.
[0129] In some embodiments, controlling the ratio of Li₂O content to TiO₂ content (Li₂O / TiO₂) within the range of 0.2 to 4.5 can effectively reduce the Ti content in glass-ceramics and glass-ceramic products. 3+ The coloring by ions improves the transmittance of glass-ceramics and glass-ceramic products, and optimizes the haze and |B| value of glass-ceramics and glass-ceramic products. Therefore, the preferred Li2O / TiO2 ratio is 0.2 to 4.5, more preferably 0.5 to 3.5, even more preferably 0.7 to 2.5, and still more preferably 0.75 to 1.5. In some embodiments, the Li₂O / TiO₂ ratio is 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, or 1. 55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5.
[0130] In some embodiments, the ratio between the total content of TiO2and ZnO and the content of Al2O3, (TiO2+ ZnO) / Al2O3, is in the range of 0.4-1.5, which can optimize the chemical strengthening performance of the glass-ceramics, increase the ion exchange depth of the glass-ceramic product, and increase the fracture toughness, four-point bending strength, and drop ball test height. Therefore, (TiO2+ ZnO) / Al2O3 is preferably in the range of 0.4-1.5, more preferably in the range of 0.5-1.2, further preferably in the range of 0.6-1.0, and more further preferably in the range of 0.6-0.9. In some embodiments, (TiO2+ ZnO) / Al2O3 is 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5.
[0131] ZrO2may be used as a nucleating agent for the glass-ceramics and glass-ceramic products, and its use together with TiO2can make the crystal nuclei of the glass-ceramics as many as possible, which is beneficial to the stable growth of the crystals and the uniformity of the grain size. If the content of ZrO2is too high, the melting of the glass will be difficult. Therefore, the content of ZrO2is in the range of 0-5%, preferably in the range of 0.5-4%, and more preferably in the range of 1-3%. In some embodiments, the glass-ceramics can contain about 0%, more than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5% of ZrO2.
[0132] Zr02has low solubility in the glass system of the present application, and in some embodiments, the solubility of Zr02in the glass can be increased by including an amount of P205; however, if too much P205is included, the glass can phase separate easily, resulting in a decrease in the chemical durability of the glass-ceramic and glass-ceramic articles. Accordingly, the amount of P205in the present application is from 0 to 5%, preferably from 0.5 to 4%, and more preferably from 1 to 3%. In some embodiments, the glass can include about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5% P205.
[0133] In some embodiments, the ratio between the total content of Al2O3 and Li2O and the content of P2O5, (Al2O3+Li2O) / P2O5, is controlled in the range of 5.0-45.0, which is beneficial to increase the four-point bending strength and drop resistance of the glass-ceramics and glass-ceramic articles, and to increase the surface stress of the glass-ceramic articles. Therefore, it is preferred that (Al2O3+Li2O) / P2O5 is in the range of 5.0-45.0, more preferably (Al2O3+Li2O) / P2O5 is in the range of 7.0-35.0, further preferably (Al2O3+Li2O) / P2O5 is in the range of 8.0-30.0, and more further preferably (Al2O3+Li2O) / P2O5 is in the range of 10.0-25.0. In some embodiments, (Al2O3+Li2O) / P2O5 is 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0, 20.5, 21.0, 21.5, 22.0, 22.5, 23.0, 23.5, 24.0, 24.5, 25.0, 26.0, 27.0, 28.0, 29.0, 30.0, 31.0, 32.0, 33.0, 34.0, 35.0, 36.0, 37.0, 38.0, 39.0, 40.0, 41.0, 42.0, 43.0, 44.0, 45.0.
[0134] In some embodiments, the total content of P2O5 and ZrO2, P2O5+ZrO2, is controlled in the range of 0-8%, which is beneficial for the glass-ceramics and glass-ceramic articles to obtain uniform grains and smaller grain size, and to optimize the transmittance of the glass-ceramics and glass-ceramic articles. Therefore, it is preferred that P2O5+ZrO2 is in the range of 0-8%, more preferably P2O5+ZrO2 is in the range of 0.1-7%, and further preferably P2O5+ZrO2 is in the range of 0.5-5%. In some embodiments, P2O5+ZrO2 is 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, 7%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5%, 7.6%, 7.7%, 7.8%, 7.9%, 8%.
[0135] In some embodiments, the ratio of the content of P2O5 to the content of ZrO2, P2O5 / ZrO2, is controlled to be in the range of 0.1 to 5.0, which is beneficial to increase the hardness and fracture toughness of the glass-ceramics and glass-ceramic articles and prevent the deterioration of the drop resistance and Young's modulus. Therefore, it is preferred that P2O5 / ZrO2 is in the range of 0.1 to 5.0, more preferably P2O5 / ZrO2 is in the range of 0.2 to 3.0, further preferably P2O5 / ZrO2 is in the range of 0.5 to 2.0, and more further preferably P2O5 / ZrO2 is in the range of 0.6 to 1.5. In some embodiments, P2O5 / ZrO2 is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0.
[0136] MgO helps to reduce the viscosity of the glass, suppresses crystallization of the glass during forming and refines the grains during crystallization, and has the effect of improving the low-temperature melting property. In some embodiments, MgO has the effect of promoting the formation of quartz solid solution crystal phase. If the content of MgO is too high, quartz solid solution crystal phase is easily generated during crystallization of the glass, and the quartz solid solution crystal phase has large grains, which can reduce the transmittance of the glass-ceramics and glass-ceramic articles. Therefore, the content of MgO is 0.1 to 6%, preferably 1 to 5%, and more preferably 2 to 4%. In some embodiments, about 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6% of MgO can be included.
[0137] In some embodiments, the ratio between the total content of Li2O and MgO and the content of TiO2, (Li2O+MgO) / TiO2, is in the range of 0.3-8.0, which can refine the grain, improve the transmittance and the drop resistance of the glass-ceramics and the glass-ceramic articles, and optimize the haze and |B| value of the glass-ceramics and the glass-ceramic articles. Therefore, it is preferred that (Li2O+MgO) / TiO2 is in the range of 0.3-8.0, more preferably (Li2O+MgO) / TiO2 is in the range of 0.5-5.0, further preferably (Li2O+MgO) / TiO2 is in the range of 1.0-3.0, and more further preferably (Li2O+MgO) / TiO2 is in the range of 1.2-2.5. In some embodiments, (Li2O+MgO) / TiO2 is 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9, 8.0.
[0138] In some embodiments, the ratio between the content of Al2O3 and the total content of MgO and TiO2, Al2O3 / (MgO+TiO2), is controlled in the range of 1.3-10.0, which is beneficial to increase the hardness and the ball drop height of the glass-ceramics and glass-ceramic articles, and to optimize the surface stress and the haze of the glass-ceramic articles. Therefore, it is preferred that Al2O3 / (MgO+TiO2) is in the range of 1.3-10.0, more preferably Al2O3 / (MgO+TiO2) is in the range of 1.5-8.0, further preferably Al2O3 / (MgO+TiO2) is in the range of 2.5-6.5, and more further preferably Al2O3 / (MgO+TiO2) is in the range of 3.0-5.5. In some embodiments, Al2O3 / (MgO+TiO2) is 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9, 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9, 9.0, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9, 10.0.
[0139] B2O3 helps the melting of the glass and improves the melting effect of the glass. If the content of B2O3 is too high, the chemical stability of the glass becomes poor, boron abnormality easily occurs, the boron oxygen tetrahedron changes to boron oxygen triangle structure, and the viscosity of the glass decreases. In addition, boron volatilization easily forms stripes, causing the glass to be non-uniform. Therefore, the content of B2O3 is 0-4%, preferably 0-2%, and more preferably 0-1%. In some embodiments, about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4% of B2O3 can be included.
[0140] Na2O can promote the melting of the glass and improve the chemical strengthening performance of the glass-ceramic. However, if too much Na2O is contained in the present application, the glass can have more broken bonds, the strength of the matrix glass can be reduced, and the strength of the glass-ceramic and the glass-ceramic product can be affected. Therefore, the upper limit of the content of Na2O in the present application is 6%, preferably the upper limit is 4%, and more preferably the upper limit is 2%. In some embodiments, about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6% of Na2O can be included.
[0141] In some embodiments, the ratio between the total content of SiO2 and Na2O and the content of ZnO, (SiO2+Na2O) / ZnO, is controlled in the range of 2.2-6.2, which can improve the fracture toughness and the extrusion strength of the glass-ceramics and glass-ceramic articles while optimizing the |B| value. Therefore, (SiO2+Na2O) / ZnO is preferably 2.2-6.2, more preferably (SiO2+Na2O) / ZnO is 2.5-6.0, further preferably (SiO2+Na2O) / ZnO is 2.8-5.5, and more further preferably (SiO2+Na2O) / ZnO is 3.0-5.0. In some embodiments, (SiO2+Na2O) / ZnO is 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2.
[0142] K2O helps to reduce the glass melting temperature, is beneficial to chemical strengthening, and can increase the ion exchange depth of the glass-ceramic articles. However, if K2O is contained in excess, it can easily result in the decrease of the chemical stability of the glass and the decrease of the hardness. Therefore, the content of K2O is 3% or less, preferably 2% or less, and more preferably 1% or less. In some embodiments, K2O can be contained in an amount of about 0%, more than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%.
[0143] In some embodiments, the ratio between the total content of Na2O and K2O, Na2O+K2O, and the content of ZnO, (Na2O+K2O) / ZnO, is controlled to be below 0.8, which can refine the grain, reduce the grain size of the glass-ceramics and glass-ceramic articles, increase the transmittance and the extrusion strength of the glass-ceramics and glass-ceramic articles, and optimize the haze of the glass-ceramics and glass-ceramic articles. Therefore, it is preferred that (Na2O+K2O) / ZnO be below 0.8, more preferably (Na2O+K2O) / ZnO be below 0.6, further preferably (Na2O+K2O) / ZnO be below 0.4, more further preferably (Na2O+K2O) / ZnO be below 0.2. In some embodiments, (Na2O+K2O) / ZnO is 0, greater than 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8.
[0144] CaO, BaO and SrO do not participate in the formation of crystalline phases as fluxing agents, remain in the residual glass phase of the glass-ceramics, and are beneficial to reduce the melting and processing temperatures, but excessive content can impair the nucleation and crystallization during the transformation of the matrix glass into glass-ceramics, and adversely affect the chemical stability of the glass-ceramics. Therefore, the total content of CaO, BaO and SrO, CaO+BaO+SrO, is 0-5%, preferably 0-4%, more preferably 0-2%. In some embodiments, CaO+BaO+SrO is 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%.
[0145] Y2O3 can promote the melting of ZrO2, reduce the difficulty of melting the glass, and when the content is too high, it can cause difficulty in forming crystals during crystallization of the glass, and the drop ball test height of the glass-ceramic and glass-ceramic article can decrease. Therefore, the upper limit of the content of Y2O3 is 6%, preferably the upper limit is 4%, and more preferably the upper limit is 2%. In some embodiments, the glass, glass-ceramic, or glass-ceramic article can include about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6% of Y2O3.
[0146] In some embodiments, the glass, glass-ceramic, or glass-ceramic article can further include 0-2% of a fining agent to improve the bubble removal ability of the glass, glass-ceramic, or glass-ceramic article. Such fining agents include, but are not limited to, one or more of Sb2O3, SnO2, SnO, CeO2, F (fluorine) compounds, Cl (chlorine) compounds, and Br (bromine) compounds, and Sb2O3 is preferred as the fining agent. When the above-mentioned fining agents exist alone or in combination, the upper limit of the content thereof is preferably 2%, more preferably the upper limit is 1%, and more preferably the upper limit is 0.5%. In some embodiments, the content of one or more of the fining agents is about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%.
[0147] In the case of not affecting the performance of the glass, glass-ceramics or glass-ceramics products of the present application, other components not mentioned above can be added appropriately, such as La2O3, Gd2O3, Yb2O3, Nb2O5, WO3, Bi2O3, Ta2O5, TeO2, etc. However, in order to maintain the excellent performance of the glass, glass-ceramics or glass-ceramics products of the present application, the content of each of La2O3, Gd2O3, Yb2O3, Nb2O5, WO3, Bi2O3, Ta2O5, TeO2 or the total content of them is preferably 5% or less, more preferably 2% or less, further preferably 1% or less, and more further preferably none.
[0148] PbO and As2O3 are toxic substances, and even a small amount of them is not in line with the environmental protection requirements, so the glass, glass-ceramics or glass-ceramics products of the present application preferably do not contain PbO and / or As2O3 in some embodiments.
[0149] In some embodiments of the present application, by containing a colorant, the substrate glass, glass-ceramics or glass-ceramics products with color can be prepared, and the substrate glass, glass-ceramics or glass-ceramics products can present different colors. The colorant contains: NiO: 0-4%; and / or Ni2O3: 0-4%; and / or CoO: 0-2%; and / or Co2O3: 0-2%; and / or Fe2O3: 0-7%; and / or MnO2: 0-4%; and / or Er2O3: 0-8%; and / or Nd2O3: 0-8%; and / or Cu2O: 0-4%; and / or Pr2O5: 0-8%; and / or CeO2: 0-4%. The weight percentage content of the colorant and its effects are described in detail as follows:
[0150] The brown or green matrix glass, glass-ceramic or glass-ceramic article prepared by the present application uses NiO, Ni2O3 or Pr2O5 as colorant. NiO and Ni2O3 are used as colorant for preparing brown or green matrix glass, glass-ceramic or glass-ceramic article, either of the two components can be used alone or in combination, each of the components is generally present in an amount of 4% or less, preferably 3% or less. If the amount exceeds 4%, the colorant cannot be well dissolved in the matrix glass, glass-ceramic or glass-ceramic article. The lower limit of the amount of each of the components is 0.1% or more. If the amount is less than 0.1%, the color of the matrix glass, glass-ceramic or glass-ceramic article is not obvious. In some embodiments, about 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% of NiO or Ni2O3 can be included. When used in combination, the total amount of NiO and Ni2O3 is generally 4% or less, and the lower limit of the total amount is 0.1% or more. In some embodiments, about 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% of NiO and Ni2O3 can be included. Pr2O5 is used as a green colorant for the matrix glass, glass-ceramic or glass-ceramic article. When used alone, the amount is generally 8% or less, preferably 6% or less. The lower limit of the amount is 0.4% or more. If the amount is less than 0.4%, the color of the matrix glass, glass-ceramic or glass-ceramic article is not obvious.In some embodiments, about 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0%, 5.2%, 5.4%, 5.6%, 5.8%, 6.0%, 6.2%, 6.4%, 6.6%, 6.8%, 7.0%, 7.2%, 7.4%, 7.6%, 7.8%, 8.0% of Pr2O5 can be included.
[0151] In some embodiments, about 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0% of CoO or Co2O3 can be included. When used in combination, the total amount of CoO and Co2O3 does not exceed 2%, and the lower limit of the total amount is more than 0.05%. In some embodiments, about 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0% of CoO and Co2O3 can be included.
[0152] The yellow matrix glass, glass-ceramic or glass-ceramic article prepared by the present application uses Cu2O or CeO2 as colorant, either of the two colorant components is used alone or in combination, and the lower limit of the content of each is above 0.5%, if the content is below 0.5%, the color of the matrix glass, glass-ceramic or glass-ceramic article is not obvious, the content of Cu2O used alone is below 4%, preferably below 3%, if the content exceeds 4%, the matrix glass is easy to crystallize. In some embodiments, about 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% of Cu2O can be included. The content of CeO2 used alone is generally below 4%, preferably below 3%, if the content exceeds 4%, the matrix glass, glass-ceramic or glass-ceramic article has poor luster. In some embodiments, about 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% of CeO2 can be included. At the same time, a small amount of CeO2 added to the glass has the effect of removing bubbles, and CeO2 can also be used as a fining agent in the glass, when used as a fining agent, the content is below 2%, preferably below 1%, more preferably below 0.5%. If the two colorants are used in combination, the total content is generally below 4%, and the lower limit of the total content is above 0.5%. In some embodiments, about 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% of CeO2 and Cu2O can be included.
[0153] The black or smoky matrix glass, glass-ceramic or glass-ceramic article prepared according to the present invention uses Fe203as a colorant alone; or uses Fe203and CoO as a colorant in combination; or uses Fe203and Co203as a colorant in combination; or uses Fe203, CoO and NiO as a colorant in combination; or uses Fe203, Co203and NiO as a colorant in combination. The colorant for the black and smoky matrix glass, glass-ceramic or glass-ceramic article is primarily Fe203, which is present in an amount of 7% or less, preferably 5% or less, with a lower limit of 0.2% or more. In some embodiments, the Fe203may be present in an amount of about 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%. CoO and Co203absorb visible light and can deepen the color of the matrix glass, glass-ceramic or glass-ceramic article. In general, when used in combination with Fe203, each of CoO and Co203is present in an amount of 0.6% or less, with a lower limit of 0.2% or more. In some embodiments, the CoO and / or Co203may be present in an amount of about 0.2%, 0.3%, 0.4%, 0.5%, 0.6%. NiO absorbs visible light and can deepen the color of the matrix glass, glass-ceramic or glass-ceramic article. In general, when used in combination, the amount of NiO is 1% or less, with a lower limit of 0.2% or more. In some embodiments, the NiO may
[0154] The purple matrix glass, glass-ceramic or glass-ceramic article prepared by the present application uses MnO2 as a colorant, the content of which is generally 4% or less, preferably 3% or less. If the content is less than 0.1%, the color of the matrix glass, glass-ceramic or glass-ceramic article is not obvious. In some embodiments, the content of MnO2 can be about 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%.
[0155] The pink matrix glass, glass-ceramic or glass-ceramic article prepared by the present application uses Er2O3 as a colorant, the content of which is generally 8% or less, preferably 6% or less. Since the rare earth element Er2O3 has low coloring efficiency, if the content exceeds 8%, the color of the matrix glass, glass-ceramic or glass-ceramic article cannot be further deepened, and the cost is increased. If the content is less than 0.4%, the color of the matrix glass, glass-ceramic or glass-ceramic article is not obvious. In some embodiments, the content of Er2O3 can be about 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0%, 5.2%, 5.4%, 5.6%, 5.8%, 6.0%, 6.2%, 6.4%, 6.6%, 6.8%, 7.0%, 7.2%, 7.4%, 7.6%, 7.8%, 8.0%.
[0156] The purple red matrix glass, glass-ceramic or glass-ceramic product prepared by the present application uses Nd2O3 as a colorant, and the content is generally below 8%, preferably below 6%. Since the rare earth element Nd2O3 has low coloring efficiency, using a content of more than 8% cannot further deepen the color of the matrix glass, glass-ceramic or glass-ceramic product, but increases the cost. The lower limit of the content is above 0.4%, and if it is lower than 0.4%, the color of the matrix glass, glass-ceramic or glass-ceramic product is not obvious. In some embodiments, about 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0%, 5.2%, 5.4%, 5.6%, 5.8%, 6.0%, 6.2%, 6.4%, 6.6%, 6.8%, 7.0%, 7.2%, 7.4%, 7.6%, 7.8%, 8.0% of Nd2O3 can be included.
[0157] The red matrix glass, glass-ceramic or glass-ceramic product prepared by the present application uses a mixed colorant of Er2O3, Nd2O3 and MnO2. Er ions in the glass have absorption at 400-500 nm, Mn ions mainly have absorption at 500 nm, and Nd ions mainly have strong absorption at 580 nm. The mixture of the three substances can prepare a red matrix glass, glass-ceramic or glass-ceramic product. Since Er2O3 and Nd2O3 are rare earth coloring, the coloring ability is relatively weak. The use amount of Er2O3 is within 6%, and the use amount of Nd2O3 is within 4%. MnO2 has strong coloring, and the use amount is within 2%. The lower limit of the total amount of the mixed colorant is above 0.9%.
[0158] The "does not contain" "0%" described herein means that the compound, molecule or element is not intentionally added as a raw material to the matrix glass, glass-ceramic or glass-ceramic product of the present application; but as a raw material and / or equipment for producing the matrix glass, glass-ceramic or glass-ceramic product, there may be some impurities or components that are not intentionally added, which may contain a small amount or trace amount in the final matrix glass, glass-ceramic or glass-ceramic product, and such a case is also within the protection scope of the present application.
[0159] In some embodiments of the present application, the microcrystalline glass and the microcrystalline glass product contain spinel crystal phase, which provides high strength for the microcrystalline glass and the microcrystalline glass product, and the fracture toughness of the microcrystalline glass and the microcrystalline glass product is high. The bulk drop height of the microcrystalline glass and the drop test height and the four-point bending strength of the microcrystalline glass product are large. The chemical strengthening performance of the microcrystalline glass of the present application is excellent, and the microcrystalline glass can be treated by a chemical strengthening process to obtain excellent mechanical strength. Through reasonable component design, the microcrystalline glass and the microcrystalline glass product of the present application can obtain a suitable grain size, so that the microcrystalline glass and the microcrystalline glass product of the present application have high strength.
[0160] In some embodiments of the present application, the grain size and the crystal phase type of the microcrystalline glass or the microcrystalline glass product affect the haze and the light transmittance of the microcrystalline glass or the microcrystalline glass product. The smaller the grain size, the higher the light transmittance. The smaller the haze, the higher the light transmittance. In some embodiments, the haze of the microcrystalline glass product or the microcrystalline glass with a thickness of less than 1 mm is less than 0.3%, preferably less than 0.25%, and more preferably 0.05-0.2%. In some embodiments, the grain size of the microcrystalline glass product or the microcrystalline glass is less than 60 nm, preferably less than 45 nm, and more preferably 10-30 nm.
[0161] In some embodiments of the present application, the crystal phase content and the refractive index of the microcrystalline glass or the microcrystalline glass product affect the |B| value of the microcrystalline glass or the microcrystalline glass product. In the visible light range, the microcrystalline glass or the microcrystalline glass product appears blue or yellow, which affects the optical performance of the product. In LAB (color value of a substance), the |B| value is used for indication. The microcrystalline glass or the microcrystalline glass product of the present application has a low |B| value in the visible light range. In some embodiments, the average light |B| value of the microcrystalline glass product or the microcrystalline glass with a thickness of less than 1 mm is less than 1.0, preferably less than 0.8, and more preferably 0.3-0.6 in the range of 400-800 nm.
[0162] In some embodiments of the present application, the microcrystalline glass or the microcrystalline glass product has high transparency in the visible light range (i.e., the microcrystalline glass or the microcrystalline glass product is transparent). The microcrystalline glass or the microcrystalline glass product has high transmittance in the visible light range. In some embodiments, the average light transmittance of the microcrystalline glass product or the microcrystalline glass with a thickness of less than 1 mm is preferably more than 87.0%, more preferably more than 88.5%, and further preferably more than 89.5% in the range of 400-800 nm. In some preferred embodiments, the light transmittance of the microcrystalline glass product or the microcrystalline glass with a thickness of less than 1 mm is preferably more than 87.0%, more preferably more than 88.0%, and further preferably more than 89.0% at 550 nm.
[0163] In some embodiments, an antimicrobial component can be added to the base glass, glass-ceramic, or glass-ceramic article. The glass-ceramics or glass-ceramic articles described herein can be used, for example, in kitchen or food service countertop applications where exposure to harmful bacteria is likely. The base glass, glass-ceramic, or glass-ceramic article can contain an antimicrobial component including, but not limited to, Ag, AgO, Cu, CuO, Cu2O, and the like. In some embodiments, the individual or combined content of the above-mentioned antimicrobial components is 2% or less, preferably 1% or less.
[0164] The base glass, glass-ceramic, and glass-ceramic articles of the present application can be produced and manufactured by the following methods:
[0165] The base glass is produced by mixing the raw materials (oxides, hydroxides, complex salts, etc.) in the proportions of the components, and then placing them in a crucible (e.g., a platinum or quartz crucible). The mixture is melted in an electric or gas furnace at a temperature in the range of 1350 to 1550°C for 5 to 24 hours, depending on the melting difficulty of the glass composition, and preferably at a temperature in the range of 1450 to 1550°C. The base glass is then obtained by refining, homogenizing, forming, and annealing the glass. The refining temperature is preferably greater than 1550°C but less than or equal to 1650°C, and the annealing temperature is preferably in the range of 450 to 600°C.
[0166] The base glass of the present application can be formed by well-known methods.
[0167] The base glass of the present application is crystallized by a crystallization process after the forming or forming process, and crystalline phases are uniformly precipitated in the glass to produce a glass-ceramic. The crystallization process can be performed in one stage or in two stages, and preferably in two stages. The two-stage crystallization process is performed by a nucleation process at a first temperature, and then a crystal growth process at a second temperature. The crystallization process performed at the first temperature is referred to as a first crystallization process, and the crystallization process performed at the second temperature is referred to as a second crystallization process.
[0168] In order to obtain desired physical and chemical properties of the glass-ceramic, the preferred crystallization process is:
[0169] The crystallization process performed in one stage can continuously perform the nucleation process and the crystal growth process. That is, the temperature is increased to a predetermined crystallization temperature, and after the crystallization temperature is reached, the temperature is maintained for a certain period of time, and then the temperature is decreased. The crystallization temperature is preferably in the range of 600 to 800°C, and more preferably in the range of 650 to 750°C in order to precipitate desired crystalline phases. The holding time at the crystallization temperature is preferably in the range of 1 to 10 hours, and more preferably in the range of 3 to 6 hours.
[0170] When the crystallization treatment is performed in two stages, the first temperature is preferably 600 to 700°C, the second temperature is preferably greater than 700°C but less than or equal to 800°C, the holding time at the first temperature is preferably 1 to 6 hours, and the holding time at the second temperature is preferably 2 to 5 hours.
[0171] In some embodiments, the substrate glass or glass-ceramic described herein can be formed into shaped bodies, including but not limited to sheets, by various processes, including but not limited to slot draw, float, rolling, and other processes known in the art for forming sheets. Alternatively, the substrate glass or glass-ceramic can be formed by float or rolling processes known in the art. The shaped bodies described herein also include lenses, prisms, and the like.
[0172] The substrate glass or glass-ceramic of the present application can be formed into a glass shaped body or a glass-ceramic shaped body by grinding or polishing, but the method of forming the glass shaped body or the glass-ceramic shaped body is not limited to these methods.
[0173] The substrate glass or glass-ceramic of the present application can be formed into a glass shaped body or a glass-ceramic shaped body in various shapes by hot bending or press forming at a certain temperature, but the method is not limited to these methods.
[0174] In some embodiments, the glass shaped body or the glass-ceramic shaped body can be formed by a hot bending process. The hot bending process is a process of placing a 2D or 2.5D glass or glass-ceramic in a mold, and sequentially performing steps including preheating by heating, press forming, pressure holding, and cooling in a hot bending machine to obtain a 3D curved glass shaped body or a glass-ceramic shaped body.
[0175] In some embodiments, the glass-ceramic shaped body has a 2.5D or 3D configuration, i.e., the glass-ceramic shaped body has a non-planar configuration. As used herein, "non-planar configuration" means that at least a portion of the glass-ceramic shaped body extends outwardly or along an angle with respect to a plane defined by the original, layout configuration of the 2D substrate glass in a 2.5D or 3D shape. The 2.5D or 3D glass-ceramic shaped body formed from the substrate glass can have one or more convex or curved portions.
[0176] In some embodiments, the method of manufacturing the glass-ceramic shaped body is a hot bending process in combination with the growth and transformation of the crystalline phase in the glass-ceramic. Specifically, the method includes pre-crystallization and hot working. The pre-crystallization of the present application is to form a pre-crystallized glass by controlling the crystallization process of the substrate glass, and the crystallinity of the pre-crystallized glass does not reach the crystallinity required by the performance index of the target glass-ceramic shaped body. The pre-crystallized glass is then formed into a glass-ceramic shaped body by a hot working process.
[0177] In some embodiments, the method for manufacturing the glass-ceramic shaped body comprises the following steps:
[0178] 1) subjecting the base glass to a primary crystallization heat treatment process comprising a temperature rising, a temperature holding nucleation, a temperature rising, a temperature holding crystallization, and a temperature falling to room temperature, to form a pre-crystallized glass;
[0179] 2) subjecting the pre-crystallized glass to a thermal forming process to obtain the glass-ceramic shaped body.
[0180] The crystallization heat treatment process according to the present application comprises subjecting the base glass to a nucleation at a temperature T h and a time t h , and subjecting the pre-crystallized glass to a crystallization at a temperature T c and a time t c . The crystallinity of the pre-crystallized glass obtained does not reach the crystallinity required by the performance index of the target glass-ceramic shaped body. The total content of the main crystal phase in the crystallinity of the pre-crystallized glass is calculated by the Rietveld full spectrum fitting refinement method based on the XRD test data, and is I c1 . The pre-crystallization according to the present application is a complete process in terms of process, which comprises one step of nucleation, one or more steps of crystallization, and is a complete process of temperature rising, temperature holding, temperature rising again, temperature holding again, and so on, and then falling to room temperature according to the process. Different from the primary crystallization, the secondary crystallization, and so on mentioned in some documents or patents, the present application is actually only the first step of crystallization in a complete crystallization process, and the second step of crystallization, and so on, which are continuous and do not have the process of falling to room temperature and then rising again for crystallization.
[0181] The thermal forming process according to the present application refers to a forming process of the pre-crystallized glass under certain temperature, time, and pressure conditions, and the thermal forming process comprises one or more thermal forming processes, which comprises but is not limited to compression forming, bending forming, or drawing forming of the pre-crystallized glass under certain temperature, time, and pressure conditions. In the thermal forming process, sometimes the shaped body with a complex shape cannot be completed by one thermal forming process, and may need to be completed by two or more thermal forming processes.
[0182] In some embodiments, the method for manufacturing the glass-ceramic shaped body is a thermal bending process. Specifically, in some embodiments, the method for manufacturing the glass-ceramic shaped body comprises the following steps:
[0183] 1) Temperature rising preheating: the base glass or pre-crystallized glass or glass-ceramic is placed in a mold, the mold is sequentially passed through each temperature rising station in a hot bending machine, and stays at each station for a certain time for heat preservation. The preheating zone temperature is 400-800°C, the pressure is 0.01-0.05 MPa, and the time is 40-200 s. In some embodiments, for a hot bending machine with 5 preheating stations, the initial temperature rising is generally set at about 500°C, the temperature gradually increases at subsequent stations, the temperature gradient between adjacent two stations gradually decreases from low to high, and the temperature difference between the last preheating station and the first forming station is within 20°C.
[0184] 2) Press forming: after preheating, the mold is transferred to a forming station, and the hot bending machine applies a certain pressure to the mold, the pressure range is 0.1-0.8 MPa, the pressure size is determined according to the glass thickness, curvature and other factors, the forming station temperature range is 600-850°C, and the forming time range is 40-200 s.
[0185] 3) Pressure holding and temperature decreasing: the mold is transferred to a temperature decreasing station for step-by-step temperature decreasing. The temperature decreasing range is controlled to be 750-500°C, the pressure is 0.01-0.05 MPa, and the time is 40-200 s.
[0186] In addition to the need to control the appearance quality of the glass-ceramic formed body like ordinary high-alumina glass, the influence of crystal growth and development on the performance of the glass-ceramic during the hot bending process also needs to be controlled, such as 3D curved glass-ceramic used for display devices or electronic device housings, which needs to closely monitor the light transmittance, haze, |B| value and uniformity after hot bending.
[0187] The base glass, glass-ceramic and glass-ceramic product described in the present application can have any reasonable and useful thickness.
[0188] In addition to improving the mechanical properties by precipitating crystals, the glass-ceramic of the present application can also obtain more excellent mechanical properties by forming a compressive stress layer, thereby making a glass-ceramic product.
[0189] In some embodiments, the base glass or glass-ceramic can be processed into a sheet and / or shaped (such as punched, hot bent, etc.), polished and / or sanded after shaping, and then chemically strengthened by a chemical strengthening process.
[0190] The chemical strengthening described in the present application is ion exchange method. In the ion exchange process, the smaller metal ions in the base glass or glass-ceramic are replaced or "exchanged" by larger metal ions with the same valence near the base glass or glass-ceramic. Replacing smaller ions with larger ions builds a compressive stress in the base glass or glass-ceramic, forming a compressive stress layer.
[0191] In some embodiments, the metal ions are monovalent alkali metal ions (e.g., Na + , K + , Rb + , Cs + , etc.), and ion exchange is performed by immersing the substrate glass or glass-ceramic in a salt bath comprising at least one molten salt of a larger metal ion that is used to replace a smaller metal ion in the substrate glass. Alternatively, other monovalent metal ions such as Ag + , Tl + , Cu + , etc. can also be used to exchange the monovalent ions. One or more ion exchange processes used to chemically strengthen the substrate glass or glass-ceramic can include, but are not limited to, immersing it in a single salt bath, or immersing it in multiple salt baths having the same or different compositions, with washing and / or annealing steps between immersions.
[0192] In some embodiments, the substrate glass or glass-ceramic can be ion exchanged by immersing in a molten Na salt (e.g., NaNO3) salt bath at a temperature of about 350-470°C for about 1-36 hours, preferably at a temperature range of 400-460°C and preferably for a time range of 2-15 hours. In this embodiment, Na ions replace some of the Li ions in the substrate glass or glass-ceramic to form a surface compressive layer and exhibit high mechanical properties. In some embodiments, the substrate glass or glass-ceramic can be ion exchanged by immersing in a mixed salt bath of molten K and Na salts at a temperature of about 360-450°C for 1-36 hours, preferably for a time range of 2-24 hours.
[0193] The glass-ceramics of the present application have high efficiency in low temperature ion exchange. In some embodiments, the depth of the exchanged layer of Na ions can reach more than 75 μm at a lower ion exchange temperature and a shorter exchange time. After ion exchange, the hardness of the glass-ceramic article is significantly improved, which is mainly due to the high compressive stress formed on the surface of the glass-ceramic article by the "crowding effect" of ion exchange, which increases the deformation resistance and improves the hardness of the glass-ceramic article. In some embodiments, the Vickers hardness of the glass-ceramic article of the present application after chemical strengthening can reach 650 kgf / mm 2 or more.
[0194] The performance indicators of the glass-ceramics and / or glass-ceramic articles of the present application are tested using the following methods:
[0195] [Cloudiness]
[0196] The cloudiness is tested using a haze tester, BenQ CM3600A, with a sample thickness of less than 1 mm, and GB2410-80 as the standard.
[0197] [crystal grain size]
[0198] The crystal grain size of the glass-ceramics is determined by surface treatment of the glass-ceramics in HF acid, gold spraying on the surface of the glass-ceramics, and surface scanning under a scanning electron microscope (SEM).
[0199] [light transmittance]
[0200] The light transmittance described herein is all external transmittance, and is sometimes simply referred to as transmittance.
[0201] The sample is processed to be below 1 mm and the opposite faces are parallel polished, and the average light transmittance at 400-800 nm is measured using a Hitachi U-41000 spectrophotometer.
[0202] The sample is processed to be below 1 mm and the opposite faces are parallel polished, and the light transmittance at 550 nm is measured using a Hitachi U-41000 spectrophotometer.
[0203] [ion exchange layer depth]
[0204] The ion exchange layer depth is measured using a glass surface stress meter SLP-2000.
[0205] The calculation is performed with a refractive index of the sample of 1.56 and an optical elastic constant of 29 [(nm / cm) / Mpa] as the measurement conditions.
[0206] [surface stress]
[0207] The surface stress is measured using a glass surface stress meter SLP-2000.
[0208] The calculation is performed with a refractive index of the sample of 1.56 and an optical elastic constant of 29 [(nm / cm) / Mpa] as the measurement conditions.
[0209] [drop resistance]
[0210] The drop resistance test was performed using a drop tester WH-2101. The drop resistance was measured by loading a glass product of the same size (2 pieces each weighing 20 g) on a 2D glass-ceramic product, laying a 60-80 grit sandpaper on the base, and dropping the sample directly on the sandpaper from a predetermined height without breaking. Specifically, the test was performed from a height of 600 mm, and the height was sequentially changed to 700 mm, 800 mm, 900 mm, 1000 mm, and above, without breaking. In the examples, the test data of 1000 mm was recorded, indicating that the glass-ceramic product with a load did not break and withstand the impact even from a height of 1000 mm. The maximum test height of the drop tester WH-2101 was 2000 mm.
[0211] [Drop ball test height]
[0212] A glass-ceramic product sample of 145 mm x 67 mm x 0.7 mm was placed on a glass loading jig, and a 132 g steel ball was dropped from a predetermined height, with the drop point being the center point of the sample. The maximum drop ball test height was measured, at which the sample did not break and withstand the impact. Specifically, the drop ball test height was started from 400 mm, and the test was performed once at each height. If the sample did not break, the test was continued by sequentially increasing the height by 100 mm until the sample broke. In the examples, the test data of 1700 mm was recorded, indicating that the glass-ceramic product did not break and withstand the impact even when the steel ball was dropped from a height of 1700 mm. In the present invention, the drop ball test height is sometimes referred to as the drop ball height.
[0213] [Fracture toughness]
[0214] The fracture strength was measured using a method of directly measuring the size of a crack extending from an indentation, with a sample size of 2 mm x 4 mm x 20 mm, and after chamfering, flattening, and polishing, a Vickers hardness indenter was used to apply a force of 49 N to the sample for 30 s, and after making an indentation, the fracture strength was measured using a three-point bending method.
[0215] [Four-point bending strength]
[0216] A microcomputer-controlled electronic universal testing machine CMT6502 was used, with a sample size of 1 mm or less in thickness (preferably 0.7 mm in thickness), and the test was performed according to ASTM C 158-2002. In the present invention, the four-point bending strength is sometimes referred to as the bending strength.
[0217] [Vickers hardness]
[0218] The value of the load (N) divided by the surface area (mm2) calculated by the length of the indentation when a diamond tetra-pyramid indenter with a relative face angle of 136° is pressed into a pyramid-shaped indentation on the test surface is expressed. The test load is 100 (N) and the holding time is 15 (sec). 2 ) is expressed. The test load is 100 (N) and the holding time is 15 (sec). In the present invention, the Vickers hardness is sometimes simply referred to as hardness.
[0219] [Anti-pressing strength]
[0220] A microcomputer-controlled electronic universal testing machine CMT6502 is used, and a 145 mm x 67 mm x 0.7 mm sample of the glass-ceramic product is placed on a glass loading fixture. A mushroom head design is used for the pressing rod, with a diameter of ¢10 mm, and the pressing speed is 5 mm / min until the sample is destroyed. Calibration is required before testing, and the test point is at the center position. The test button is clicked until the glass-ceramic product sample is crushed by pressing, and the pressure (N) at which the sample is crushed is recorded. For the examples with "anti-pressing strength", the glass-ceramic product is used as the test object. In the examples, the test data of 500 N is recorded, indicating that the maximum pressing force before the glass-ceramic product is crushed is 500 N.
[0221] [|B| value]
[0222] A Brother CM-700d is used for B value detection. The sample size is less than 1 mm thick, and the instrument zero calibration and whiteboard calibration are performed using the matching calibration long cylinder and short cylinder. After calibration, the long cylinder is used for empty testing to determine the stability and reliability of the instrument calibration (B≤0.05). After the instrument calibration is qualified, the product is placed on the zero long cylinder for testing.
[0223] The |B| value is the absolute value of the B value.
[0224] [Young's modulus]
[0225] The Young's modulus (E) is calculated according to the following formula by testing the longitudinal wave speed and transverse wave speed using ultrasonic waves.
[0226]
[0227] G = V S 2 ρ
[0228] In the formula: E is the Young's modulus, Pa;
[0229] G is the shear modulus, Pa;
[0230] V T is the transverse wave speed, m / s;
[0231] V S is the longitudinal wave speed, m / s;
[0232] p is the density of the glass, g / cm 3 .
[0233] The microcrystalline glass product has the following properties:
[0234] 1) In some embodiments, the grain size of the microcrystalline glass product is 60 nm or less, preferably 45 nm or less, and more preferably 10-30 nm.
[0235] 2) In some embodiments, the ion exchange layer depth of the microcrystalline glass product is 75 μm or more, preferably 80-150 μm, and more preferably 100-125 μm.
[0236] 3) In some embodiments, the surface stress of the microcrystalline glass product is 200 MPa or more, preferably 250-400 MPa, and more preferably 300-400 MPa.
[0237] 4) In some embodiments, the drop ball test height of the microcrystalline glass product is 1000 mm or more, preferably 1200 mm or more, and more preferably 1500 mm or more.
[0238] 5) In some embodiments, the drop resistance of the microcrystalline glass product is 1200 mm or more, preferably 1300 mm or more, and more preferably 1400 mm or more.
[0239] 6) In some embodiments, the fracture toughness of the microcrystalline glass product is 1.0 MPa·m 1 / 2 or more, preferably 1.2 MPa·m 1 / 2 or more, and more preferably 1.2-1.6 MPa·m 1 / 2 .
[0240] 7) In some embodiments, the four-point bending strength of the microcrystalline glass product is 500 MPa or more, preferably 600 MPa or more, and more preferably 700-1000 MPa.
[0241] 8) In some embodiments, the extrusion resistance of the microcrystalline glass product is 400 N or more, preferably 400-550 N, and more preferably 450-550 N.
[0242] 9) In some embodiments, the Vickers hardness (H v ) of the microcrystalline glass product is 650 kgf / mm 2 or more, preferably 660 kgf / mm 2 or more, and more preferably 680-750 kgf / mm 2 .
[0243] 10) In some embodiments, the haze of the microcrystalline glass article is 0.3% or less, preferably 0.25% or less, more preferably 0.05 to 0.2%, for thicknesses of 1 mm or less. Preferably, the thickness is 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, even more preferably 0.5 to 0.8 mm, and still more preferably 0.55 mm or 0.6 mm or 0.68 mm or 0.7 mm or 0.75 mm.
[0244] 11) In some embodiments, the average light transmission of the microcrystalline glass article is 87.0% or more, preferably 88.5% or more, more preferably 89.5% or more, for wavelengths of 400 to 800 nm, for thicknesses of 1 mm or less. Preferably, the thickness is 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, even more preferably 0.5 to 0.8 mm, and still more preferably 0.55 mm or 0.6 mm or 0.68 mm or 0.7 mm or 0.75 mm.
[0245] 12) In some embodiments, the light transmission of the microcrystalline glass article is 87.0% or more, preferably 88.0% or more, more preferably 89.0% or more, for a wavelength of 550 nm, for thicknesses of 1 mm or less. Preferably, the thickness is 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, even more preferably 0.5 to 0.8 mm, and still more preferably 0.55 mm or 0.6 mm or 0.68 mm or 0.7 mm or 0.75 mm.
[0246] 13) In some embodiments, the average light ∣B∣ value of the microcrystalline glass article is 1.0 or less, preferably 0.8 or less, more preferably 0.3 to 0.6, for wavelengths of 400 to 800 nm, for thicknesses of 1 mm or less. Preferably, the thickness is 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, even more preferably 0.5 to 0.8 mm, and still more preferably 0.55 mm or 0.6 mm or 0.68 mm or 0.7 mm or 0.75 mm.
[0247] The microcrystalline glass of the present application has the following properties:
[0248] 1) In some embodiments, the grain size of the microcrystalline glass is 60 nm or less, preferably 45 nm or less, more preferably 10 to 30 nm.
[0249] 2) In some embodiments, the haze of the microcrystalline glass is 0.3% or less, preferably 0.25% or less, more preferably 0.05 to 0.2%, for thicknesses of 1 mm or less. Preferably, the thickness is 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, even more preferably 0.5 to 0.8 mm, and still more preferably 0.55 mm or 0.6 mm or 0.68 mm or 0.7 mm or 0.75 mm.
[0250] 3) In some embodiments, the microcrystalline glass having a thickness of 1 mm or less has an average light transmittance of 87.0% or more, preferably 88.5% or more, more preferably 89.5% or more, at a wavelength of 400 to 800 nm. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, further preferably 0.5 to 0.8 mm, more further preferably 0.55 mm or 0.6 mm or 0.68 mm or 0.7 mm or 0.75 mm.
[0251] 4) In some embodiments, the microcrystalline glass having a thickness of 1 mm or less has a light transmittance of 87.0% or more, preferably 88.0% or more, more preferably 89.0% or more, at a wavelength of 550 nm. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, further preferably 0.5 to 0.8 mm, more further preferably 0.55 mm or 0.6 mm or 0.68 mm or 0.7 mm or 0.75 mm.
[0252] 5) In some embodiments, the microcrystalline glass having a thickness of 1 mm or less has an average light ∣B∣ value of 1.0 or less, preferably 0.8 or less, more preferably 0.3 to 0.6, at a wavelength of 400 to 800 nm. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, further preferably 0.5 to 0.8 mm, more further preferably 0.55 mm or 0.6 mm or 0.68 mm or 0.7 mm or 0.75 mm.
[0253] 6) In some embodiments, the microcrystalline glass has a Young's modulus (E) of 80 to 110 GPa, preferably 85 to 105 GPa, more preferably 90 to 105 GPa.
[0254] 7) In some embodiments, the microcrystalline glass has a Vickers hardness (H v ) of 550 kgf / mm 2 or more, preferably 580 kgf / mm 2 or more, more preferably 600 to 650 kgf / mm 2 .
[0255] The microcrystalline glass, the microcrystalline glass product, the matrix glass, the glass forming body and the microcrystalline glass forming body of the present application can be widely made into glass cover plates or glass components due to the excellent performance. Meanwhile, the microcrystalline glass, the microcrystalline glass product, the matrix glass, the glass forming body and the microcrystalline glass forming body of the present application can be applied to electronic devices or display devices, such as mobile phones, watches, computers, touch display screens, etc., for manufacturing protective glass of mobile phones, smart phones, tablet computers, notebook computers, PDAs, televisions, personal computers, MTA machines or industrial displays, or for manufacturing touch screens, protective windows, automobile windows, train windows, aviation machinery windows, touch screen protective glass, or for manufacturing hard disk substrates or solar cell substrates, or for manufacturing white household appliances, such as for manufacturing refrigerator parts or kitchen utensils.
[0256] Embodiment
[0257] In order to further clarify and illustrate the technical solutions of the present application, the following non-limiting embodiments are provided. The embodiments of the present application have been made through many efforts to ensure the accuracy of the values (such as the amount, temperature, etc.), but it must be considered that there are some errors and deviations. The composition itself is given in weight % based on oxide, and has been standardized to 100%.
[0258] <Microcrystalline glass embodiment>
[0259] This embodiment uses the above-mentioned microcrystalline glass manufacturing method to obtain microcrystalline glass with the composition shown in Tables 1-4. In addition, the properties of each microcrystalline glass are determined by the test method described in the present application, and the test results are shown in Tables 1-4. The thickness of the test sample for haze, average light transmittance at 400-800 nm wavelength, light transmittance at 550 nm wavelength, and average light |B| value at 400-800 nm in the following embodiments is 0.7 mm.
[0260] Table 1.
[0261]
[0262]
[0263] Table 2.
[0264]
[0265]
[0266] Table 3.
[0267]
[0268]
[0269] Table 4.
[0270]
[0271]
[0272] <Example of Glass-Ceramic Product>
[0273] The glass-ceramic products having the compositions shown in Tables 5 to 8 were obtained by the above-described method for manufacturing a glass-ceramic product. In addition, the properties of each glass-ceramic product were measured by the test methods described in the present application, and the measurement results are shown in Tables 5 to 8. The thickness of the test sample for measuring the haze, the average light transmittance in the wavelength of 400 to 800 nm, the light transmittance at the wavelength of 550 nm, and the average light |B| value in the wavelength of 400 to 800 nm in the following examples was 0.7 mm.
[0274] Table 5.
[0275]
[0276]
[0277] Table 6.
[0278]
[0279]
[0280] Table 7.
[0281]
[0282]
[0283]
[0284] Table 8.
[0285]
[0286]
Claims
1. A glass-ceramic article, characterized in that, The components, expressed in percentage by weight, comprise: SiO2: 40-55%; Al2O3: 21-30%; Li2O: 0.1-6%; ZnO: 9-20%; MgO: 0.1-6%; TiO2: 0.5-7%; Na2O: 0-4%, Al2O3 / ZnO is 1.6-3.0, (Na2O+K2O) / ZnO is 0.6 or less, Al2O3 / (MgO+TiO2) is 4.0-6.5, Al2O3+ZnO is 34-45%, (SiO2+Na2O) / ZnO is 2.2-6.2, (Li2O+MgO) / TiO2 is 0.3-8.0, SiO2 / Al2O3 is 1.5-2.45, the average light transmittance of the glass-ceramic product with a thickness of 1mm or less at a wavelength of 400-800nm is 88.5% or more, and the haze of the glass-ceramic product with a thickness of 1mm or less is 0.3% or less. The components, expressed in percentage by weight, further comprise: P2O5+ZrO2: 0-8%; and / or B2O3: 0-4%; and / or K2O: 0-3%; and / or CaO+BaO+SrO: 0-5%; and / or Y2O3: 0-6%; and / or clarifier: 0-2%. The components, expressed in percentage by weight, comprise: SiO2: 40-55%; Al2O3: 21-30%; ZnO: 9-20%; TiO2: 0.5-7%; Na2O: 0-4%, the glass-ceramic product contains spinel crystal phase, the falling resistance of the glass-ceramic product is 1200mm or more, Al2O3 / ZnO is 1.6-3.0, (Na2O+K2O) / ZnO is 0.6 or less, Al2O3 / (MgO+TiO2) is 4.0-6.5, Al2O3+ZnO is 34-45%, (SiO2+Na2O) / ZnO is 2.2-6.2, (Li2O+MgO) / TiO2 is 0.3-8.0, SiO2 / Al2O3 is 1.5-2.45, the average light transmittance of the glass-ceramic product with a thickness of 1mm or less at a wavelength of 400-800nm is 88.5% or more, and the haze of the glass-ceramic product with a thickness of 1mm or less is 0.3% or less.
2. The glass-ceramic article of claim 1, wherein, The components, expressed in percentage by weight, comprise: Li2O: 0.1-6%; and / or MgO: 0.1-6%; and / or P2O5+ZrO2: 0-8%; and / or B2O3: 0-4%; and / or K2O: 0-3%; and / or CaO+BaO+SrO: 0-5%; and / or Y2O3: 0-6%; and / or clarifier: 0-2%.
3. A glass-ceramic article, characterized in that, The components, expressed in percentage by weight, satisfy one or more of the following 7 situations:
4. The glass-ceramic article of claim 3, wherein, 1) Li2O / TiO2 is 0.2-4.5; 5. The glass-ceramic article according to any one of claims 1 to 4, characterized in that, 2) Al2O3+ZnO is 34-42%; 3) Al2O3 / ZnO is 1.6-2.8; 4) SiO2 / Al2O3 is 1.7-2.45; 5) (TiO2+ZnO) / Al2O3 is 0.4-1.5; 6) (Li2O+MgO) / TiO2 is 0.5-5.0; 7) Al2O3 / (MgO+TiO2) is 4.0-5.
5.
6. The glass-ceramic article according to any one of claims 1 to 4, characterized in that, The components are represented by weight percentage, and meet one or more of the following six situations: 1) Li2O / TiO2 is 0.5-3.5; 2) Al2O3+ZnO is 35-40%; 3) Al2O3 / ZnO is 1.6-2.5; 4) SiO2 / Al2O3 is 1.8-2.45; 5) (TiO2+ZnO) / Al2O3 is 0.5-1.2; 6) (Li2O+MgO) / TiO2 is 1.0-3.
0.
7. The glass-ceramic article according to any one of claims 1 to 4, characterized in that, The components are represented by weight percentage, and meet one or more of the following five situations: 1) Li2O / TiO2 is 0.7-2.5; 2) Al2O3 / ZnO is 1.6-2.3; 3) SiO2 / Al2O3 is 2.0-2.45; 4) (TiO2+ZnO) / Al2O3 is 0.6-1.0; 5) (Li2O+MgO) / TiO2 is 1.2-2.
5.
8. The glass-ceramic article of any of claims 1 to 4, wherein, The components are represented by weight percentage, and meet one or more of the following two situations: 1) Li2O / TiO2 is 0.75-1.5; 2) (TiO2+ZnO) / Al2O3 is 0.6-0.
9.
9. The glass-ceramic article of any of claims 1 to 4, wherein, The components are represented by weight percentage, and meet one or more of the following four situations: 1) (Al2O3+Li2O) / P2O5 is 5.0-45.0; 2) P2O5 / ZrO2 is 0.1-5.0; 3) (SiO2+Na2O) / ZnO is 2.5-6.0; 4) (Na2O+K2O) / ZnO is 0.4 or less.
10. The glass-ceramic article of any of claims 1 to 4, wherein, The components are represented by weight percentage, and meet one or more of the following four situations: 1) (Al2O3+Li2O) / P2O5 is 7.0-35.0; 2) P2O5 / ZrO2 is 0.2-3.0; 3) (SiO2+Na2O) / ZnO is 2.8-5.5; 4) (Na2O+K2O) / ZnO is 0.2 or less.
11. The glass-ceramic article of any of claims 1 to 4, wherein, The components are represented by weight percentage, and meet one or more of the following three situations: 1) (Al2O3+Li2O) / P2O5 is 8.0-30.0; 2) P2O5 / ZrO2 is 0.5-2.0; 3) (SiO2+Na2O) / ZnO is 3.0-5.
0.
12. The glass-ceramic article of any of claims 1 to 4, wherein, The components are represented by weight percentage, and meet one or more of the following two situations: 1) (Al2O3+Li2O) / P2O5 is 10.0-25.0; 2) P2O5 / ZrO2 is 0.6-1.
5.
13. The glass-ceramic article of any of claims 1 to 4, wherein, comprise, by weight percent: SiO2: 45-53%; and / or Al2O3: 21-25%; and / or Li2O: 1-5%; and / or ZnO: 11-18%; and / or MgO: 1-5%; and / or TiO2: 1-6%; and / or P2O5+ZrO2: 0.1-7%; and / or Na2O: 0-2%; and / or B2O3: 0-2%; and / or K2O: 0-2%; and / or CaO+BaO+SrO: 0-4%; and / or Y2O3: 0-4%; and / or fining agent: 0-1%.
14. The glass-ceramic article of any of claims 1 to 4, wherein, comprise, by weight percent: SiO2: 48-52%; and / or Al2O3: 21-23%; and / or Li2O: 2-4%; and / or ZnO: 12-16%; and / or MgO: 2-4%; and / or TiO2: 2-5%; and / or P2O5+ZrO2: 0.5-5%; and / or B2O3: 0-1%; and / or K2O: 0-1%; and / or CaO+BaO+SrO: 0-2%; and / or Y2O3: 0-2%; and / or fining agent: 0-0.5%.
15. The glass-ceramic article of any of claims 1 to 4, wherein, comprise, by weight percent: P2O5: 0-5%; and / or ZrO2: 0-5%.
16. The glass-ceramic article of any of claims 1 to 4, wherein, comprise, by weight percent: P2O5: 0.5-4%; and / or ZrO2: 0.5-4%.
17. The glass-ceramic article of any of claims 1 to 4, wherein, comprise, by weight percent: P2O5: 1-3%; and / or ZrO2: 1-3%.
18. The glass-ceramic article of any of claims 1 to 4, wherein, The glass-ceramic article comprises a spinel crystalline phase.
19. The glass-ceramic article of any of claims 1 to 4, wherein, The glass-ceramic article comprises a spinel crystalline phase, the spinel crystalline phase having a higher weight percentage than other crystalline phases.
20. The glass-ceramic article of any of claims 1 to 4, wherein, The glass-ceramic article comprises a spinel crystalline phase, the spinel crystalline phase having a weight percentage of 20-60% of the glass-ceramic article.
21. The glass-ceramic article of any of claims 1 to 4, wherein, The glass-ceramic article comprises a spinel crystalline phase, the spinel crystalline phase having a weight percentage of 25-50% of the glass-ceramic article.
22. The glass-ceramic article of any of claims 1 to 4, wherein, The glass-ceramic article comprises a spinel crystalline phase, the spinel crystalline phase having a weight percentage of 25-45% of the glass-ceramic article.
23. The glass-ceramic article of any of claims 1 to 4, wherein, The glass-ceramic article comprises a spinel crystalline phase, the spinel crystalline phase having a weight percentage of 30-45% of the glass-ceramic article.
24. The glass-ceramic article of any of claims 1 to 4, wherein, The glass-ceramic article comprises a quartz crystalline phase.
25. The glass-ceramic article of any of claims 1 to 4, wherein, The glass-ceramic article comprises a quartz crystalline phase, the quartz crystalline phase having a weight percentage of 20% or less of the glass-ceramic article.
26. The glass-ceramic article of any of claims 1 to 4, wherein, The glass-ceramic article comprises a quartz crystalline phase, the quartz crystalline phase having a weight percentage of 10% or less of the glass-ceramic article.
27. The glass-ceramic article of any of claims 1 to 4, wherein, The glass-ceramic article comprises a quartz crystalline phase, the quartz crystalline phase having a weight percentage of 5% or less of the glass-ceramic article.
28. The glass-ceramic article of any of claims 1 to 4, wherein, The glass-ceramic article does not comprise a quartz crystalline phase.
29. The glass-ceramic article of any of claims 1 to 4, wherein, comprise, by weight percent: La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-5%.
30. The glass-ceramic article of any of claims 1 to 4, wherein, The components, in terms of percentage by weight, comprise: La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-2%.
31. The glass-ceramic article of any of claims 1 to 4, wherein, The components, in terms of percentage by weight, comprise: La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-1%.
32. The glass-ceramic article of any of claims 1 to 4, wherein, La2O3 is not contained, and / or Gd2O3 is not contained, and / or Yb2O3 is not contained, and / or Nb2O5 is not contained, and / or WO3 is not contained, and / or Bi2O3 is not contained, and / or Ta2O5 is not contained, and / or TeO2 is not contained.
33. The glass-ceramic article of any of claims 1 to 4, wherein, The microcrystalline glass product has a grain size of 60 nm or less; and / or an ion exchange layer depth of 75 μm or more; and / or a surface stress of 200 MPa or more; and / or a drop ball test height of 1000 mm or more; and / or a drop resistance of 1200 mm or more; and / or a fracture toughness of 1.0 MPa·m 1 / 2 or more; and / or a four-point bending strength of 500 MPa or more; and / or a crush strength of 400 N or more; and / or a Vickers hardness of 650 kgf / mm 2 or more.
34. The glass-ceramic article of any of claims 1 to 4, wherein, The grain size of the glass-ceramic product is below 45 nm; and / or the ion exchange layer depth is 80-150 μm; and / or the surface stress is 250-400 MPa; and / or the drop ball test height is above 1200 mm; and / or the drop resistance is above 1300 mm; and / or the fracture toughness is above 1.2 MPa·m 1 / 2 above; and / or the four-point bending strength is above 600 MPa; and / or the extrusion resistance is 400-550 N; and / or the Vickers hardness is above 660 kgf / mm 2 above.
35. The glass-ceramic article of any of claims 1 to 4, wherein, The grain size of the glass-ceramic product is 10-30 nm; and / or the ion exchange layer depth is 100-125 μm; and / or the surface stress is 300-400 MPa; and / or the drop ball test height is 1500 mm or more; and / or the drop resistance is 1400 mm or more; and / or the fracture toughness is 1.2-1.6 MPa·m 1 / 2 ; and / or the four-point bending strength is 700-1000 MPa; and / or the extrusion resistance is 450-550 N; and / or the Vickers hardness is 680-750 kgf / mm 2 .
36. The glass-ceramic article of any of claims 1 to 4, wherein, The haze of the glass-ceramic product with a thickness of 1 mm or less is 0.25% or less; and / or the average light transmittance in the wavelength of 400-800 nm is 89.5% or more; and / or the light transmittance at the wavelength of 550 nm is 87.0% or more; and / or the average light ∣B∣ value in the wavelength of 400-800 nm is 1.0 or less.
37. The glass-ceramic article of any of claims 1 to 4, wherein, The haze of the glass-ceramic product with a thickness of 1 mm or less is 0.05-0.2%; and / or the light transmittance at the wavelength of 550 nm is 88.0% or more; and / or the average light ∣B∣ value in the wavelength of 400-800 nm is 0.8 or less.
38. The glass-ceramic article of any of claims 1 to 4, wherein, The light transmittance at the wavelength of 550 nm of the glass-ceramic product with a thickness of 1 mm or less is 89.0% or more; and / or the average light ∣B∣ value in the wavelength of 400-800 nm is 0.3-0.
6.
39. The glass-ceramic article of claim 36, wherein, The thickness of the glass-ceramic product is 0.2-1 mm.
40. The glass-ceramic article of claim 36, wherein, The thickness of the glass-ceramic product is 0.3-0.9 mm.
41. The glass-ceramic article of Claim 36 wherein, The thickness of the glass-ceramic product is 0.5-0.8 mm.
42. The glass-ceramic article of Claim 36 wherein, The thickness of the glass-ceramic product is 0.55 mm or 0.6 mm or 0.68 mm or 0.7 mm or 0.75 mm.
43. The glass-ceramic article of any of claims 1 to 4, wherein, The components, in terms of percentage by weight, comprise: NiO: 0-4%; and / or Ni2O3: 0-4%; and / or CoO: 0-2%; and / or Co2O3: 0-2%; and / or Fe2O3: 0-7%; and / or MnO2: 0-4%; and / or Er2O3: 0-8%; and / or Nd2O3: 0-8%; and / or Cu2O: 0-4%; and / or Pr2O3: 0-8%; and / or CeO2: 0-4%.
44. Glass-ceramic, characterized in that, The components, in terms of percentage by weight, comprise: SiO2: 40-55%; Al2O3: 21-30%; Li2O: 0.1-6%; ZnO: 9-20%; MgO: 0.1-6%; TiO2: 0.5-7%; Na2O: 0-4%, Al2O3 / ZnO is 1.6-3.0, (Na2O+K2O) / ZnO is 0.6 or less, Al2O3 / (MgO+TiO2) is 4.0-6.5, Al2O3+ZnO is 34-45%, (SiO2+Na2O) / ZnO is 2.2-6.2, (Li2O+MgO) / TiO2 is 0.3-8.0, SiO2 / Al2O3 is 1.5-2.45, the average light transmittance of the glass-ceramic product with a thickness of less than 1mm at a wavelength of 400-800nm is 88.5% or more, and the haze of the glass-ceramic product with a thickness of less than 1mm is 0.3% or less.
45. The glass-ceramic according to claim 44, wherein, The components are represented by weight percentage, further comprising: P2O5+ZrO2: 0-8%; and / or B2O3: 0-4%; and / or K2O: 0-3%; and / or CaO+BaO+SrO: 0-5%; and / or Y2O3: 0-6%; and / or clarifier: 0-2%.
46. Glass-ceramic, characterized in that, The components of the glass-ceramics contain SiO2, Al2O3, ZnO and TiO2, wherein, expressed in percentage by weight, SiO2: 40-55%; Al2O3: 21-30%; ZnO: 9-20%; TiO2: 0.5-7%; Na2O: 0-4%, the glass-ceramics contains spinel crystal phase, the Vickers hardness of the glass-ceramics is 550 kgf / mm 2 The above, Al2O3 / ZnO is 1.6-3.0, (Na2O+K2O) / ZnO is 0.6 or less, Al2O3 / (MgO+TiO2) is 4.0-6.5, Al2O3+ZnO is 34-45%, (SiO2+Na2O) / ZnO is 2.2-6.2, (Li2O+MgO) / TiO2 is 0.3-8.0, SiO2 / Al2O3 is 1.5-2.45, the average light transmittance of the glass-ceramics product with a thickness of 1mm or less at a wavelength of 400-800nm is 88.5% or more, and the haze of the glass-ceramics product with a thickness of 1mm or less is 0.3% or less.
47. The glass-ceramic according to claim 46, wherein, The components are represented by weight percentage, comprising: Li2O: 0.1-6%; and / or MgO: 0.1-6%; and / or P2O5+ZrO2: 0-8%; and / or B2O3: 0-4%; and / or K2O: 0-3%; and / or CaO+BaO+SrO: 0-5%; and / or Y2O3: 0-6%; and / or clarifier: 0-2%.
48. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The components are represented by weight percentage, satisfying one or more of the following 7 cases: 1) Li2O / TiO2 is 0.2-4.5; 2) Al2O3+ZnO is 34-42%; 3) Al2O3 / ZnO is 1.6-2.8; 4) SiO2 / Al2O3 is 1.7-2.45; 5) (TiO2+ZnO) / Al2O3 is 0.4-1.5; 6) (Li2O+MgO) / TiO2 is 0.5-5.0; 7) Al2O3 / (MgO+TiO2) is 4.0-5.
5.
49. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The components are represented by weight percentage, satisfying one or more of the following 6 cases: 1) Li2O / TiO2 is 0.5-3.5; 2) Al2O3+ZnO is 35-40%; 3) Al2O3 / ZnO is 1.6-2.5; 4) SiO2 / Al2O3 is 1.8-2.45; 5) (TiO2+ZnO) / Al2O3 is 0.5-1.2; 6) (Li2O+MgO) / TiO2 is 1.0-3.
0.
50. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The components are represented by weight percentage, satisfying one or more of the following 5 cases: 1) Li2O / TiO2 is 0.7-2.5; 2) Al2O3 / ZnO is 1.6-2.3; 3) SiO2 / Al2O3 is 2.0-2.45; 4) (TiO2+ZnO) / Al2O3 is 0.6-1.0; 5) (Li2O+MgO) / TiO2 is 1.2-2.
5.
51. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The components are represented by weight percentage, satisfying one or more of the following 2 cases: 1) Li2O / TiO2 is 0.75 to 1.5; 2) (TiO2+ZnO) / Al2O3 is 0.6 to 0.
9.
52. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The components thereof, expressed in percentage by weight, satisfy one or more of the following four situations: 1) (Al2O3+Li2O) / P2O5 is 5.0 to 45.0; 2) P2O5 / ZrO2 is 0.1 to 5.0; 3) (SiO2+Na2O) / ZnO is 2.5 to 6.0; 4) (Na2O+K2O) / ZnO is 0.4 or less.
53. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The components thereof, expressed in percentage by weight, satisfy one or more of the following four situations: 1) (Al2O3+Li2O) / P2O5 is 7.0 to 35.0; 2) P2O5 / ZrO2 is 0.2 to 3.0; 3) (SiO2+Na2O) / ZnO is 2.8 to 5.5; 4) (Na2O+K2O) / ZnO is 0.2 or less.
54. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The components thereof, expressed in percentage by weight, satisfy one or more of the following three situations: 1) (Al2O3+Li2O) / P2O5 is 8.0 to 30.0; 2) P2O5 / ZrO2 is 0.5 to 2.0; 3) (SiO2+Na2O) / ZnO is 3.0 to 5.
0.
55. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The components thereof, expressed in percentage by weight, satisfy one or more of the following two situations: 1) (Al2O3+Li2O) / P2O5 is 10.0 to 25.0; 2) P2O5 / ZrO2 is 0.6 to 1.
5.
56. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The components thereof, expressed in percentage by weight, contain: SiO2: 45 to 53%; and / or Al2O3: 21 to 25%; and / or Li2O: 1 to 5%; and / or ZnO: 11 to 18%; and / or MgO: 1 to 5%; and / or TiO2: 1 to 6%; and / or P2O5+ZrO2: 0.1 to 7%; and / or Na2O: 0 to 2%; and / or B2O3: 0 to 2%; and / or K2O: 0 to 2%; and / or CaO+BaO+SrO: 0 to 4%; and / or Y2O3: 0 to 4%; and / or clarifier: 0 to 1%.
57. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The components thereof, expressed in percentage by weight, contain: SiO2: 48 to 52%; and / or Al2O3: 21 to 23%; and / or Li2O: 2 to 4%; and / or ZnO: 12 to 16%; and / or MgO: 2 to 4%; and / or TiO2: 2 to 5%; and / or P2O5+ZrO2: 0.5 to 5%; and / or B2O3: 0 to 1%; and / or K2O: 0 to 1%; and / or CaO+BaO+SrO: 0 to 2%; and / or Y2O3: 0 to 2%; and / or clarifier: 0 to 0.5%.
58. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The components thereof, expressed in percentage by weight, contain: P2O5: 0 to 5%; and / or ZrO2: 0 to 5%.
59. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The components thereof, expressed in percentage by weight, contain: P2O5: 0.5 to 4%; and / or ZrO2: 0.5 to 4%.
60. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The components thereof, expressed in percentage by weight, contain: P2O5: 1 to 3%; and / or ZrO2: 1 to 3%.
61. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The said glass-ceramics contain spinel crystalline phase.
62. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The microcrystalline glass contains a spinel crystal phase, and the spinel crystal phase has a higher weight percentage than other crystal phases.
63. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The microcrystalline glass contains a spinel crystal phase, and the weight percentage of the spinel crystal phase in the microcrystalline glass is 20-60%.
64. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The microcrystalline glass contains a spinel crystal phase, and the weight percentage of the spinel crystal phase in the microcrystalline glass is 25-50%.
65. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The microcrystalline glass contains a spinel crystal phase, and the weight percentage of the spinel crystal phase in the microcrystalline glass is 25-45%.
66. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The microcrystalline glass contains a spinel crystal phase, and the weight percentage of the spinel crystal phase in the microcrystalline glass is 30-45%.
67. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The microcrystalline glass contains a quartz crystal phase.
68. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The microcrystalline glass contains a quartz crystal phase, and the weight percentage of the quartz crystal phase in the microcrystalline glass is 20% or less.
69. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The microcrystalline glass contains a quartz crystal phase, and the weight percentage of the quartz crystal phase in the microcrystalline glass is 10% or less.
70. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The microcrystalline glass contains a quartz crystal phase, and the weight percentage of the quartz crystal phase in the microcrystalline glass is 5% or less.
71. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The microcrystalline glass does not contain a quartz crystal phase.
72. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The components are represented by weight percentage, and contain: La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-5%.
73. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The components are represented by weight percentage, and contain: La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-2%.
74. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The components are represented by weight percentage, and contain: La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-1%.
75. The glass-ceramic according to any one of claims 44 to 47, characterized in that, Do not contain La2O3, and / or do not contain Gd2O3, and / or do not contain Yb2O3, and / or do not contain Nb2O5, and / or do not contain WO3, and / or do not contain Bi2O3, and / or do not contain Ta2O5, and / or do not contain TeO2.
76. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The microcrystalline glass has a grain size of 60 nm or less; and / or a Young's modulus of 80-110 GPa; and / or a Vickers hardness of 550 kgf / mm 2 The above.
77. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The microcrystalline glass has a grain size of 45 nm or less; and / or a Young's modulus of 85-105 GPa; and / or a Vickers hardness of 580 kgf / mm 2 The above.
78. The glass-ceramic according to any one of claims 44 to 47, characterized in that The microcrystalline glass has a grain size of 10-30 nm; and / or a Young's modulus of 90-105 GPa; and / or a Vickers hardness of 600-650 kgf / mm 2 .
79. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The haze of the microcrystalline glass with a thickness of 1mm or less is 0.25% or less; and / or the average light transmittance at a wavelength of 400-800nm is 88.5% or more; and / or the light transmittance at a wavelength of 550nm is 87.0% or more; and / or the average light ∣B∣ value at 400-800nm is 1.0 or less.
80. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The haze of the microcrystalline glass with a thickness of 1mm or less is 0.05-0.2%; and / or the average light transmittance at a wavelength of 400-800nm is 89.5% or more; and / or the light transmittance at a wavelength of 550nm is 88.0% or more; and / or the average light ∣B∣ value at 400-800nm is 0.8 or less.
81. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The light transmittance at a wavelength of 550nm of the microcrystalline glass with a thickness of 1mm or less is 89.0% or more; and / or the average light ∣B∣ value at 400-800nm is 0.3-0.
6.
82. The glass-ceramic according to claim 79, wherein The thickness of the microcrystalline glass is 0.2-1mm.
83. The glass-ceramic according to claim 79, wherein The thickness of the microcrystalline glass is 0.3-0.9mm.
84. The glass-ceramic according to claim 79, wherein The thickness of the microcrystalline glass is 0.5-0.8mm.
85. The glass-ceramic according to claim 79, wherein The thickness of the microcrystalline glass is 0.55mm or 0.6mm or 0.68mm or 0.7mm or 0.75mm.
86. The glass-ceramic according to any one of claims 44 to 47, characterized in that, The components are expressed in percentage by weight and comprise: NiO: 0-4%; and / or Ni2O3: 0-4%; and / or CoO: 0-2%; and / or Co2O3: 0-2%; and / or Fe2O3: 0-7%; and / or MnO2: 0-4%; and / or Er2O3: 0-8%; and / or Nd2O3: 0-8%; and / or Cu2O: 0-4%; and / or Pr2O3: 0-8%; and / or CeO2: 0-4%.
87. A glass-ceramic shaped body, characterized in that The glass-ceramic according to any one of claims 44 to 86.
88. A glass cover plate characterized by, The glass-ceramic article according to any one of claims 1 to 43, and / or the glass-ceramic according to any one of claims 44 to 86, and / or the glass-ceramic shaped body according to claim 87.
89. A glass component, characterized by, The glass-ceramic article according to any one of claims 1 to 43, and / or the glass-ceramic according to any one of claims 44 to 86, and / or the glass-ceramic shaped body according to claim 87.
90. An electronic device, comprising: The glass-ceramic article according to any one of claims 1 to 43, and / or the glass-ceramic according to any one of claims 44 to 86, and / or the glass-ceramic shaped body according to claim 87, and / or the glass cover plate according to claim 88, and / or the glass component according to claim 89.
91. A display device, characterized by The glass-ceramic article according to any one of claims 1 to 43, and / or the glass-ceramic according to any one of claims 44 to 86, and / or the glass-ceramic shaped body according to claim 87, and / or the glass cover plate according to claim 88, and / or the glass component according to claim 89.
92. A method of making the glass-ceramic article of any one of claims 1 to 43, wherein The method comprises the steps of forming a base glass, forming the base glass into a glass-ceramic by a crystallization process, and forming the glass-ceramic into a glass-ceramic article by a chemical strengthening process.
93. The method of producing a glass-ceramic article according to claim 92, wherein The forming of the base glass comprises the steps of: The raw materials are mixed according to the component ratio, then put into a crucible, melted in an electric furnace or gas furnace at a temperature ranging from 1350 to 1550 °C for 5 to 24 hours, then subjected to fining, homogenization, shaping, and annealing to obtain the base glass, wherein the fining temperature is greater than 1550 °C but less than or equal to 1650 °C, and the annealing temperature is 450 to 600 °C.
94. The method of making a glass-ceramic article according to claim 92, wherein The forming of the base glass comprises the steps of: The raw materials are mixed according to the component ratio, then put into a crucible, melted in an electric furnace or gas furnace at a temperature ranging from 1450 to 1550 °C for 5 to 24 hours, then subjected to fining, homogenization, shaping, and annealing to obtain the base glass, wherein the fining temperature is greater than 1550 °C but less than or equal to 1650 °C, and the annealing temperature is 450 to 600 °C.
95. The method of making a glass-ceramic article according to claim 92, wherein The crystallization process comprises the steps of: increasing the temperature to a specified crystallization treatment temperature, maintaining the temperature at the crystallization treatment temperature for a certain period of time after reaching the crystallization treatment temperature, and then decreasing the temperature, wherein the crystallization treatment temperature is 600 to 800 °C, and the maintaining time at the crystallization treatment temperature is 1 to 10 hours.
96. The method of producing a glass-ceramic article according to claim 92, wherein The crystallization process includes the steps of increasing the temperature to a prescribed crystallization treatment temperature, maintaining the temperature at the crystallization treatment temperature for a prescribed period of time after the crystallization treatment temperature is reached, and then decreasing the temperature, the crystallization treatment temperature being 650 to 750°C, and the period of time at the crystallization treatment temperature being 3 to 6 hours.
97. The method of producing a glass-ceramic article according to claim 92, wherein The crystallization process includes the steps of performing a nucleation process at a first temperature, and then performing a crystal growth process at a second temperature.
98. The method of producing a glass-ceramic article according to claim 97, wherein The crystallization process includes the steps of performing a nucleation process at a first temperature, and then performing a crystal growth process at a second temperature.
99. The method of producing a glass-ceramic article according to claim 92, wherein The chemical strengthening process includes immersing the glass-ceramic in a molten Na salt bath at 350 to 470°C for 1 to 36 hours, preferably at 400 to 460°C for 2 to 15 hours, and / or immersing the glass-ceramic in a mixed molten K and Na salt bath at 360 to 450°C for 1 to 36 hours, preferably for 2 to 24 hours.
100. The method of making a glass-ceramic article according to claim 92, wherein The chemical strengthening process includes immersing the glass-ceramic in a molten Na salt bath at 400 to 460°C for 2 to 15 hours, and / or immersing the glass-ceramic in a mixed molten K and Na salt bath at 360 to 450°C for 2 to 24 hours.
101. The method of producing the glass-ceramic according to any one of claims 44 to 86, characterized in that, The method includes the steps of forming a base glass, and then forming the glass-ceramic from the base glass by a crystallization process.
102. The method of claim 101, wherein the glass-ceramic is produced by the method of claim 100. The forming of the base glass includes the steps of: The raw materials are mixed in the prescribed proportions, and then melted in an electric or gas furnace at a temperature of 1350 to 1550°C for 5 to 24 hours, and then the base glass is obtained by performing fining at a temperature of greater than 1550°C but less than or equal to 1650°C, homogenizing, forming, and annealing at a temperature of 450 to 600°C.
103. The method of claim 101, wherein the glass-ceramic is produced by the method of claim 100. The forming of the base glass includes the steps of: The raw materials are mixed in the prescribed proportions, and then melted in an electric or gas furnace at a temperature of 1450 to 1550°C for 5 to 24 hours, and then the base glass is obtained by performing fining at a temperature of greater than 1550°C but less than or equal to 1650°C, homogenizing, forming, and annealing at a temperature of 450 to 600°C.
104. The method of claim 101, wherein the glass-ceramic is produced by the method of claim 100. The crystallization process includes the steps of increasing the temperature to a prescribed crystallization treatment temperature, maintaining the temperature at the crystallization treatment temperature for a prescribed period of time after the crystallization treatment temperature is reached, and then decreasing the temperature, the crystallization treatment temperature being 600 to 800°C, and the period of time at the crystallization treatment temperature being 1 to 10 hours.
105. The method of claim 101, wherein the glass-ceramic is produced by the method of claim 100. The crystallization process includes the steps of increasing the temperature to a prescribed crystallization treatment temperature, maintaining the temperature at the crystallization treatment temperature for a prescribed period of time after the crystallization treatment temperature is reached, and then decreasing the temperature, the crystallization treatment temperature being 650 to 750°C, and the period of time at the crystallization treatment temperature being 3 to 6 hours.
106. The method of producing a glass-ceramic article according to claim 101, wherein The crystallization process includes the steps of performing a nucleation process at a first temperature, and then performing a crystal growth process at a second temperature.
107. The method of making a glass-ceramic article according to claim 106, wherein The crystallization process comprises: a first temperature of 600-700 DEG C, a second temperature of greater than 700 DEG C but less than or equal to 800 DEG C, a holding time at the first temperature of 1-6 hours, and a holding time at the second temperature of 2-5 hours.
108. The method of producing a glass-ceramic shaped body according to claim 87, wherein The method comprises grinding or polishing the glass-ceramic to form a glass-ceramic shaped body, or subjecting the base glass or the glass-ceramic to a hot bending process or a press forming process at a certain temperature to form the glass-ceramic shaped body.
109. The method of producing a glass-ceramic shaped body according to claim 108, wherein The method comprises the following steps: subjecting the base glass to a first crystallization heat treatment process, comprising temperature rising, nucleation, temperature rising, crystallization, and temperature falling to room temperature, to form a pre-crystallized glass; and subjecting the pre-crystallized glass to hot working to form the glass-ceramic shaped body.
110. The method of producing a glass-ceramic shaped body according to claim 108, wherein The method comprises the following steps: 1) temperature rising and preheating: the base glass or the pre-crystallized glass or the glass-ceramic is placed in a mold, the mold is sequentially passed through each temperature rising station in a hot bending machine, and is kept at each station for a certain time for temperature preservation, the preheating zone temperature is 400-800 DEG C, the pressure is 0.01-0.05 MPa, and the time is 40-200 s; 2) press forming: after preheating, the mold is transferred to a forming station, and the hot bending machine applies a certain pressure to the mold, the pressure range is 0.1-0.8 MPa, the forming station temperature range is 600-850 DEG C, and the forming time range is 40-200 s; 3) pressure keeping and temperature falling: the mold is transferred to a temperature falling station and is sequentially cooled, the temperature falling temperature range is 750-500 DEG C, the pressure is 0.01-0.05 MPa, and the time is 40-200 s.
Citation Information
Patent Citations
Crystallized glass substrate for information recording medium and method of producing the same
CN101905952A
Glass ceramic, glass ceramic product and manufacturing method thereof
CN114907014A
Tempered glass, microcrystalline glass and preparation method and application thereof
CN115286251A
Cited By
Chemically strengthened microcrystalline glass and preparation thereof
CN121672942A
Chemically strengthened microcrystalline glass and preparation thereof
CN121672942B
Precursor glass for preparing spinel glass ceramics
CN121698567A
Spinel glass ceramic and preparation method thereof
CN121698570A
Spinel microcrystalline glass and preparation method thereof
CN121698570B